Core-shell particles having non-porous core and porous shell

By using surface porous composite particles, including nonporous polymer cores and porous organic-inorganic hybrid shell materials, the problem of instability of existing chromatographic separation materials under high pH conditions is solved, and efficient separation of small molecules and large molecules is achieved.

CN119744198APending Publication Date: 2025-04-01WATERS TECHNOLOGY CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380061255.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-26
Filing Date
2023-02-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing chromatographic separation materials are unstable under high pH conditions, making it difficult to achieve efficient separation of small molecules and large molecules.

Method used

The surface porous composite particles are used, including non-porous polymer cores and porous organic-inorganic hybrid shell materials, and the stability and separation efficiency of particles are improved through the use of modified surfaces and bonding materials.

Benefits of technology

Stabilized under high pH conditions, improving the separation efficiency of small and large molecules, extending the retention time, and improving peak shape and column efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119744198A_ABST
    Figure CN119744198A_ABST
Patent Text Reader

Abstract

The present disclosure relates to core-shell particles that are surface porous, polymer-based, and include an organic-inorganic material. In various embodiments, the non-porous polymer core is surface-modified. In various embodiments, a non-porous organic-inorganic hybrid material is in contact with the modified surface of the core, and a porous organic-inorganic hybrid material is in contact with the non-porous organic-inorganic hybrid material. The present disclosure relates to chromatographic separation devices comprising such core-shell particles.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of U.S. Provisional Application Serial No. 63 / 401,556, filed on August 26, 2022, entitled “Core-Shell Particles With Organic Polymer Cores And Non-Porous Hybrid Organic-Inorganic Layers”. The entirety of the aforementioned application is incorporated herein by reference. Technical Field

[0003] The present technology relates to chromatographic materials. More specifically, the present technology relates to surface porous composite particles for chromatographic separation. Generally speaking, the surface porous composite particles include a non-porous polymer core, a non-porous organic-inorganic hybrid material in contact with the core, and a porous organic-inorganic hybrid shell material in contact with the non-porous organic-inorganic hybrid material. Background Art

[0004] Chromatography is a separation method involving two phases, one being the stationary phase and the other being the mobile phase. Typically, the stationary phase is porous or non-porous particles packed into a column. The mobile phase flows through the packed column. The sample or analyte to be separated is injected at the beginning of the column and is transported through the system by the mobile phase. As they pass through the column, the different components of the sample are distributed according to their relative affinities for the two phases. The results of the chromatographic separation are then depicted via a chromatogram, where the sample components can be identified by the various peaks or patterns in the chromatogram.

[0005] Measuring the degree of separation between two components is often referred to as the resolution of each component. Resolution can be determined by the efficiency, selectivity, and retention of the separation process. Efficiency refers to the quality of separation of the sample components and is usually determined by the number of separable peaks in the chromatogram. Selectivity refers to the ability of the chromatography to separate the sample components and is usually measured by the retention ratio of the two peaks in question in the chromatogram and can be visualized as the distance between the apexes of the two peaks. Retention or retention time refers to the time it takes for a sample to pass through the chromatographic column and is usually measured as the time interval between the injection of the sample and the detection of its components on the chromatogram.

[0006] Adjusting the mobile phase pH is a powerful tool to improve the retention and selectivity of analytes, especially ionizable analytes, in chromatographic separations. In reversed-phase chromatographic separations of basic compounds, peptides, and biological samples, high pH mobile phases combined with high temperatures are often used to obtain extended retention, excellent peak shape, and good efficiency. Silica-based stationary phases have been preferred in the past due to their stability at neutral pH and high temperatures. However, a common disadvantage is that silica-based stationary phases are unstable at high pH due to dissolution-induced particle corrosion, which in turn limits its use in these applications. An alternative to silica-based stationary phases is to use polymer-based stationary materials. Polymer-based stationary particles have shown some promise, but still have some limitations in terms of column efficiency, especially in the separation of small molecules.

[0007] Mass transfer and lateral diffusion properties are extremely important in the high resolution separation of small and large analytes. Compared with fully porous stationary phase particles, the surface porous particles commonly referred to as core-shell particles have a much shorter analyte path of travel. Therefore, the peak broadening caused by mass transfer is minimized. At present, commercially available core-shell particles are made of silicon dioxide (i.e. based on silicon dioxide), and their stability under alkaline conditions is impaired. Therefore, it is necessary to use particles for stationary phases, which have the ability to remain stable and obtain the high efficiency separation of analytes at high pH. Summary of the invention

[0008] The present technology relates to superficially porous composite particles for chromatographic separations. In particular, embodiments of the present technology relate to chromatographic separations of small and large biomolecules.

[0009] The technology disclosed herein relates to surface porous composite particles (e.g., stationary phase) for chromatographic separation. The surface porous composite particles of the present technology include a non-porous internal part and a porous external part. The porous part is generally located outside the surface porous composite particles to form a shell around the non-porous internal part. In one embodiment, the surface porous composite particles are core-shell particles including a non-porous polymer core with a modified surface. Non-porous organic-inorganic hybrid materials are deposited or formed on the modified surface of the non-porous polymer core. In order to provide porosity, the porous organic-inorganic hybrid shell material is contacted with the non-porous organic-inorganic hybrid material. The embodiment of the surface porous composite particles of the present technology may be characterized by a bonding material in addition. For example, the porous organic-inorganic hybrid shell material can be intrinsically modified (i.e., included in the shell material) with a bonding material and / or the outer surface of the porous organic-inorganic hybrid shell material can be surface modified to include a bonding material on the outermost surface area of ​​the core-shell particles. By using such superficially porous particles in the stationary phase of chromatographic separations, the superficially porous particles can remain stable at high pH and achieve high resolution separations of small molecules (such as those with a molecular weight less than 1500 Daltons) or macromolecules with a molecular weight above 1500 Daltons.

[0010] In one aspect, the present technology relates to a core-shell particle, which includes a nonporous polymer particle core having a modified surface, a nonporous organic-inorganic hybrid material in contact with the modified surface, and a porous organic-inorganic hybrid shell material in contact with the nonporous organic-inorganic hybrid material.

[0011] The above aspects may include one or more of the following features. In some embodiments, the nonporous polymer particle core of the core-shell particle is made of one or more free radical polymerizable monomers. In some embodiments, the nonporous polymer particle core is made of styrene, divinylbenzene, methacrylate or acrylonitrile. In some embodiments, the nonporous polymer particle core is made of one or more monomers containing at least two functional groups. In some embodiments, the nonporous polymer particles are prepared by condensation of monomers. In some embodiments, the monomer is a carboxylic acid / alcohol or a carboxylic acid / amine. In some embodiments, the nonporous polymer particle core is made of one or more monomers that can be polymerized by ring-opening polymerization. In some embodiments, the monomer is an epoxide. In some embodiments, at least a portion of the modified surface of the nonporous polymer particle core includes at least one functional group covalently bonded to a nonporous organic-inorganic hybrid material to form a functionalized surface. In some embodiments, the functional group is at least one of an organic silane characterized by C-Si, an organic titanium characterized by C-Ti, and an organic zirconium characterized by a C-Zr bond. In some embodiments, at least a portion of the modified surface of the nonporous polymer particle core includes at least one functional group that electrostatically interacts with the nonporous organic-inorganic hybrid material to form a functionalized surface. In some embodiments, the functional group is an amide.

[0012] The additional features of the above aspects may include one or more of the following features. In some embodiments, the nonporous organic-inorganic hybrid material of the core-shell particles has a thickness in the range of about 10nm to about 200nm. In some embodiments, the nonporous organic-inorganic hybrid material has a thickness in the range of about 25nm to about 100nm. In some embodiments, the nonporous organic-inorganic hybrid material has a pore volume less than 0.1cc / g (e.g., 0.05cc / g). In some embodiments, the nonporous organic-inorganic hybrid material includes at least one of silicon dioxide, aluminum oxide, titanium, cerium, zirconium, zirconium oxide or ceramic materials. In some embodiments, the nonporous organic-inorganic hybrid material includes an organic-inorganic hybrid material based on silicon.

[0013] On the other hand, the present technology relates to a core-shell particle, which includes a nonporous polymer particle core having a modified surface, a nonporous organic-inorganic hybrid material in contact with the modified surface, a porous organic-inorganic hybrid shell material in contact with the nonporous organic-inorganic hybrid material, and a bonding material in contact with the porous organic-inorganic hybrid shell material.

[0014] The above aspects may include one or more of the following features. In some embodiments, the binding material of the core-shell particles is incorporated in the porous organic-inorganic hybrid shell material. In some embodiments, the binding material is further deposited on the outer surface of the porous organic-inorganic hybrid shell material. In some embodiments, the binding material is uniformly incorporated. In some embodiments, the binding material is incorporated in a gradient form. In some embodiments, the binding material is further contacted with the non-porous organic-inorganic hybrid material. In some embodiments, the binding material is incorporated in the non-porous organic-inorganic hybrid material, deposited on the outer surface of the non-porous organic-inorganic hybrid material, or a combination thereof. In some embodiments, the binding material is uniformly incorporated in the non-porous organic-inorganic hybrid material. In some embodiments, the non-porous organic-inorganic hybrid material is in a gradient form. In some embodiments, the binding material is further contacted with the modified surface. In some embodiments, the binding material is incorporated in the modified surface, deposited on the modified surface, or a combination thereof. In some embodiments, the binding material is uniformly incorporated in the modified surface. In some embodiments, the bonding material is incorporated into the modified surface in a gradient.

[0015] The present technology provides multiple advantages that are superior to current chromatographic separation means. For example, the high resolution separation of DNA fragments can be provided using the surface porous composite particles described herein. That is, the surface porous particles having a non-porous core with a modified surface, a non-porous organic-inorganic hybrid material contacted with a modified surface (such as a silyl-modified surface) and a porous organic-inorganic hybrid shell material contacted with the non-porous organic-inorganic hybrid material can provide a better small molecule separation than the means used in the current industry. The present technology can remain stable at high pH. Therefore, the chromatographic separation using core-shell particles described herein can result in extended retention, better peak shape and high efficiency of small molecules and macromolecule separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0016]

[0011] The foregoing features and advantages and other features and advantages provided by the present technology will be fully understood from the following description of exemplary embodiments when read in conjunction with the accompanying drawings.

[0017] Those skilled in the art will appreciate that the drawings are primarily for illustrative purposes and are not intended to limit the scope of the inventive subject matter described herein. The drawings are not necessarily drawn to scale; in some cases, various aspects of the inventive subject matter disclosed herein may be exaggerated or enlarged in the drawings to facilitate understanding of different features. In the drawings, the same reference numerals generally represent the same features (e.g., functionally similar and / or structurally similar elements).

[0018] Figure 1 is a schematic cross-sectional view of a core-shell composite particle according to an embodiment of the present disclosure.

[0019] Figure 2 is a schematic cross-sectional view of a core-shell composite particle according to an embodiment of the present disclosure.

[0020] Figure 3 is a schematic cross-sectional view of a core-shell composite particle according to an embodiment of the present disclosure.

[0021] Figure 4 is a schematic cross-sectional view of a core-shell composite particle according to an embodiment of the present disclosure.

[0022] Figure 5 is a schematic cross-sectional view of a core-shell composite particle according to an embodiment of the present disclosure.

[0023] Figure 6 The relationship between volume and particle diameter is illustrated for Example 2 according to the present disclosure.

[0024] Figure 7 is a scanning electron micrograph of a particle cross-section of an intact particle formed according to Sample 2C of the present disclosure.

[0025] Figure 8 is a scanning electron micrograph of intact particles formed according to sample 4G.

[0026] Fig. 9 is a scanning electron micrograph of a particle cross section of a complete particle formed according to Sample 4G.

[0027] Fig.10 is a scanning electron micrograph of intact particles formed according to sample 4H.

[0028] Fig.11 is a scanning electron micrograph of a particle cross section of a complete particle formed according to sample 4H.

[0029] Fig.12 is a scanning electron micrograph of intact particles formed according to sample 4I.

[0030] Fig.13 is a scanning electron micrograph of a particle cross section of a complete particle formed according to Sample 4I.

[0031] Fig.14 is a scanning electron microscope photograph of intact particles made according to Example 3 of the present disclosure.

[0032] Fig.15 is a magnified scanning electron microscope photograph of intact particles made according to Example 3 of the present disclosure.

[0033] Fig.16 is a scanning electron micrograph of intact particles formed according to Sample 4G of the present disclosure and subsequently primed with poly(N-vinylpyrrolidone).

[0034] Fig.17 is a magnified scanning electron micrograph of an intact particle formed according to Sample 4H of the present disclosure and subsequently primed with poly(N-vinylpyrrolidone).

[0035] Fig.18 is a scanning electron micrograph of a particle cross section of a complete particle formed according to Sample 6D.

[0036] Fig.19 is a scanning electron micrograph of a particle cross section of a complete particle formed according to sample 6H.

[0037] Fig. 20 is a magnified scanning electron microscope photograph of an intact particle formed according to Sample 6A of the present disclosure.

[0038] Fig.21 is a scanning electron microscope photograph of intact particles formed according to Sample 6A of the present disclosure.

[0039] Fig. 22 is a magnified scanning electron micrograph of an intact particle formed according to Sample 6A of the present disclosure, wherein a porous hybrid shell material is added.

[0040] Fig.23 is a scanning electron micrograph of an intact particle formed according to Sample 6A of the present disclosure, wherein a porous hybrid shell material is added.

[0041] Fig.24 is a magnified scanning electron microscope photograph of intact particles formed according to Example 9.

[0042] Fig.25 is a magnified scanning electron micrograph of a cross section of a particle formed according to Example 9.

[0043] Fig.26 is a chromatogram providing the results of separation of a mixture of thiourea, naphthalene, and acenaphthene using a column packed with particles according to Example 10.

[0044] Fig.27A is a chromatogram providing the results of separation of 18-fragment dsDNA using a column packed with conventional silica core-shell particles.

[0045] Fig.27B The invention provides a method for separating 18 fragments of dsDNA (with Fig.27A Chromatogram of the results of the same sample used in ).

[0046] Fig.28Ais a chromatogram showing the result of allowing a buffer solution of pH=8.0 to flow through a column filled with the particles according to Example 10 at a flow rate of 0.2 mL / min for 15 hours.

[0047] Fig.28B is a chromatogram showing the result of allowing a buffer solution of pH=10.5 to flow through a column filled with the particles according to Example 10 at a flow rate of 0.2 mL / min for 15 hours.

[0048] Fig.28C is a chromatogram showing the result of allowing a buffer solution of pH=12.5 to flow through a column filled with the particles according to Example 10 at a flow rate of 0.2 mL / min for 15 hours.

[0049] Fig.29A This is a chromatogram showing the result of allowing a buffer solution of pH=8.0 to flow through a column filled with silica core-shell at a flow rate of 0.2 mL / min for 15 hours.

[0050] Fig.29B This is a chromatogram showing the result of allowing a buffer solution of pH=10.5 to flow through a column filled with silica core-shell at a flow rate of 0.2 mL / min for 15 hours.

[0051] Fig.29C This is a chromatogram showing the result of allowing a buffer solution of pH=12.5 to flow through a column filled with silica core-shell at a flow rate of 0.2 mL / min for 15 hours. DETAILED DESCRIPTION

[0052] The present disclosure relates to surface porous composite particles, which include a nonporous polymer particle core with a modified surface, a nonporous organic-inorganic hybrid material in contact with the modified surface, and a porous organic-inorganic hybrid shell material in contact with the nonporous organic-inorganic hybrid material. That is, an embodiment of the present disclosure relates to a core-shell particle, which includes a nonporous polymer (e.g., an organic material) particle core comprising a modified surface (e.g., a silyl-modified surface of a nonporous polymer core), an organic-inorganic hybrid nonporous material in contact with the modified surface, and a porous organic-inorganic hybrid shell material in contact with the nonporous organic-inorganic hybrid material. In some embodiments, the surface porous composite particles of the present disclosure further include a bonding material in contact with the modified surface, the nonporous organic-inorganic hybrid material, and / or the porous organic-inorganic hybrid shell material.

[0053] In some embodiments, the modified surface, nonporous organic-inorganic hybrid material, porous organic-inorganic hybrid shell material and / or bonding material are silyl-modified surfaces comprising a first functional group (i.e., reactive silane) and a second functional group (i.e., an organic polymerizable group). In certain embodiments, the modified surface is covalently bonded and / or electrostatically bonded to the nonporous organic-inorganic hybrid material. In certain embodiments, the nonporous organic-inorganic hybrid material includes (e.g., modified with a bonding material intrinsically) a bonding material. In certain embodiments, the bonding material is chemically and / or electrostatically bonded to the nonporous organic-inorganic hybrid material.

[0054] like Figures 1 to 5 As shown, a core-shell particle (100; 200; 300; 400; 500) according to an embodiment of the present disclosure is provided. The core-shell particle (100; 200; 300; 400; 500) has a non-porous polymer particle core (110; 210; 310; 410; 510), a modified surface (120; 220; 320; 420; 520) on the non-porous polymer particle core (110; 210; 310; 410; 510), a non-porous organic-inorganic hybrid material (130; 230; 330; 430; 530) and a porous organic-inorganic hybrid shell material (150; 250; 350; 450; 550). The porous organic-inorganic hybrid shell material (150; 250; 350; 450; 550) can be deposited or grown on the non-porous organic-inorganic hybrid material (130; 230; 330; 430; 530). The non-porous organic-inorganic hybrid material (130; 230; 330; 430; 530) can be deposited or grown on the modified surface (120; 220; 320; 420; 520). The modified surface (120; 220; 320; 420; 520), the non-porous organic-inorganic hybrid material (130; 230; 330; 430; 530), and / or the porous organic-inorganic hybrid shell material (250; 350; 450; 550) may include a binding material (240; 340a; 340b; 440a; 440b; 540). The binding material (240; 340a; 440a) may be bonded to the outermost surface of the porous organic-inorganic hybrid shell material (250; 350; 450) and extend beyond the outermost surface. The binding material may be formed on the porous organic-inorganic hybrid shell material by surface derivatization, the porous organic-inorganic porous shell material may be intrinsically modified with the binding material, or a combination thereof. The binding material may be customized with a material tuned for a particular type of chromatographic separation mode.

[0055] The core-shell particles of the present disclosure are generally spherical. The diameter of the core-shell particles of the present disclosure is generally in the range of 1 micron to 14 microns, more generally in the range of 1 micron to 6 microns. The particle diameter is measured herein by dispersing the sample in methanol containing 5% lithium chloride using a Coulter counter (Beckman Coulter, Multisizer 4e Coulter Counter, Brea, CA, USA). For each sample, a count of more than 70,000 particles was run using a 30 μm hole in volume mode. Using the Coulter principle, the volume of the particle is converted into a diameter, wherein the particle diameter is an equivalent spherical diameter, and the equivalent spherical diameter is the diameter of a sphere having the same volume as the volume of the particle. The particle diameter is measured as the 50% cumulative diameter of the particle size distribution based on volume.

[0056] In some embodiments, the core-shell particles of the present disclosure have good stability even at pH greater than 12 and less than 1. For example, in one embodiment, the core-shell particles according to the present technology exhibit less than 4% weight loss after exposure to an aqueous solution at a pH of 12.3 for 12 hours. Columns filled with these core-shell particles and exposed to alkaline conditions show minimal loss in separation performance.

[0057] The core-shell particles of the present disclosure are also generally narrowly distributed in size. As defined herein, a collection of particles is "narrowly distributed in size" when the ratio of the 90% cumulative volume diameter divided by the 10% cumulative volume diameter is less than 1.4 when measured with a Beckman Coulter, Multisizer 4e Coulter Counter.

[0058] Nonporous polymer core

[0059] The polymer particle core (e.g., 110, Figure 1 ) comprises at least one organic polymer. The organic polymer core typically contains greater than 95% organic polymer, more typically greater than 97.5% organic polymer, and even more typically greater than 99% organic polymer.

[0060] The polymer particle core is non-porous, which is defined herein to mean that the polymer particle core has a pore volume of less than 0.1 cc / g. Preferably, in some embodiments, the organic polymer core has a pore volume of less than 0.05 cc / g, preferably less than 0.02 cc / g. The pore volume is determined based on a multi-point nitrogen adsorption experiment (Micromeritics ASAP2400; Micromeritics Instruments Inc., Norcross, GA) using methods known in the art.

[0061] The diameter of the polymer core is typically in the range of, for example, 1 micron to 10 microns, more typically 1 micron to 5 microns. The polymer core is typically of narrow size distribution.

[0062] Basically, the polymer particle cores for use in the present disclosure include those composed of carbon and hydrogen, those composed of carbon, hydrogen and oxygen, those composed of carbon, hydrogen and nitrogen, and those composed of carbon, hydrogen, nitrogen and oxygen. The backbone of the organic polymer chain forming the polymer core may contain CC, CO, CN and / or ON covalent bonds. In some embodiments (e.g., in the case of polymers formed by free radical polymerization of vinyl groups), the backbone of at least one organic polymer chain may contain only CC covalent bonds.

[0063] As mentioned above, the polymer core for the present disclosure comprises at least one organic polymer. The at least one organic polymer comprises the residues of one or more organic monomers. The one or more organic monomer residues forming the at least one organic polymer may be selected from the residues of hydrophobic organic monomers, the residues of hydrophilic organic monomers, or a mixture of the residues of hydrophobic organic monomers and the residues of hydrophilic organic monomers.

[0064] The hydrophobic organic monomer may be selected from, for example, C2-C18 olefin monomers and / or monomers including C6-C18 monocyclic or polycyclic carbocyclic groups (e.g., phenyl groups, phenylene groups, naphthalene groups, etc.). Specific examples of hydrophobic organic monomers include, for example, monofunctional and polyfunctional aromatic monomers such as styrene, alkyl-substituted styrene, halogen-substituted styrene, divinylbenzene, and vinylbenzyl chloride; monofunctional and polyfunctional olefin monomers such as ethylene, propylene, or butylene; monofunctional and polyfunctional fluorinated monomers such as vinyl fluoride, 1,1-(difluoroethylene), tetrafluoroethylene, trifluorochloroethylene, hexafluoropropylene, perfluoropropyl vinyl ether, or perfluoromethyl vinyl ether; monomers having higher alkyl or carbon atoms; Monofunctional or multifunctional acrylate monomers having a cyclic group, for example, a monofunctional or multifunctional acrylate monomer having a C6-C18 alkyl, alkenyl or alkynyl group or a C6-C18 saturated, unsaturated or aromatic carbocyclic group; monofunctional or multifunctional methacrylate monomers having a higher alkyl or carbocyclic group, for example, a monofunctional or multifunctional methacrylate monomer having a C6-C18 alkyl, alkenyl or alkynyl group or a C6-C18 saturated, unsaturated or aromatic carbocyclic group, and the like.

[0065] The hydrophilic organic monomer can be selected from, for example, a monofunctional or multifunctional organic monomer having an amide group, a monofunctional or multifunctional organic monomer having an ester group, a monofunctional or multifunctional organic monomer having a carbonate group, a monofunctional or multifunctional organic monomer having a carbamate group, a monofunctional or multifunctional organic monomer having a urea group, a monofunctional or multifunctional organic monomer having a hydroxyl group, and a monofunctional or multifunctional organic monomer having a nitrogen-containing heterocyclic group, etc. Specific examples of the hydrophilic organic monomer include, for example, vinyl pyridine, N-vinyl pyrrolidone, N-vinyl piperidone, N-vinyl caprolactam, lower alkyl acrylates (e.g., methyl acrylate, ethyl acrylate, etc.), lower alkyl methacrylates (e.g., methyl methacrylate, ethyl methacrylate, etc.), vinyl acetate, acrylamide or methacrylamide monomers, hydroxypolyethoxy allyl ether monomers, ethoxyethyl methacrylate, glycidyl methacrylate, ethylene glycol dimethacrylate, methylenebisacrylamide, allyl methacrylate, or diallyl maleate.

[0066] In various embodiments, the nonporous polymer core includes residues of a multifunctional hydrophobic organic monomer such as divinylbenzene and / or a multifunctional hydrophilic organic monomer such as ethylene glycol dimethacrylate, methylenebisacrylamide, or allyl methacrylate to provide crosslinking in the organic copolymer. In certain embodiments, DVB 80 may be employed, which is an organic monomer mixture comprising divinylbenzene (80%) and a mixture of ethyl-styrene isomers, diethylbenzene, and may also include other isomers.

[0067] In various embodiments, the polymer core may include only residues of multifunctional organic monomers. In various embodiments, the polymer may include residues of both multifunctional organic monomers and monofunctional organic monomers.

[0068] The present inventors have discovered that in some embodiments, the porosity of a material formed from a polymer containing multifunctional organic monomer residues can be reduced by adding monofunctional organic monomer residues to the polymer, or the porosity of a material formed from a polymer containing multifunctional organic monomer residues and monofunctional organic monomer residues can be reduced by increasing the amount of monofunctional organic monomer residues relative to the multifunctional organic monomer residues in the polymer. For example, it has been found that a polymer particle core formed from DVB 80 (which is formed from an organic polymer containing 80% multifunctional divinylbenzene monomer residues and monofunctional ethylstyrene monomer residues, as described above) has a porosity of about 0.015 cc / g, while an organic polymer core formed from DVB 80 and styrene (which contains multifunctional divinylbenzene monomer residues, monofunctional ethylstyrene monomer residues, and additional monofunctional styrene monomer residues) has a porosity of less than 0.007 cc / g.

[0069] In some embodiments, a polymer particle core is produced, wherein the central region of the core is formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, and the outer region of the core is formed by an organic homopolymer containing only a multifunctional organic monomer residue. In some embodiments, an organic polymer core is produced, wherein the central region of the core is formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, and the outer region of the core is also formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, but wherein the molar ratio of the multifunctional organic monomer residue in the outer core region to the monofunctional organic monomer residue is increased relative to the central core region. In a specific example, an organic polymer core is produced, wherein the central region of the core is formed by DVB and styrene, and the outer region of the core is formed by DVB. In other embodiments, relative to the central core region, the molar ratio of the multifunctional organic monomer residue in the outer core region to the monofunctional organic monomer residue is reduced.

[0070] In various embodiments, the entire polymer particle core may be formed from an organic polymer comprising residues of a multifunctional organic monomer but not residues of a monofunctional organic monomer. In various embodiments, the entire polymer particle core may be formed from an organic polymer comprising residues of both multifunctional organic monomers and monofunctional organic monomers.

[0071] The polymer forming the polymer particle core can be prepared by a variety of methods and mechanisms, including, but not limited to, chain addition and stepwise condensation methods, free radical, anionic, cationic, ring opening, group transfer, metathesis, and photochemical mechanisms. In a particularly advantageous embodiment, the nonporous polymer particle core is prepared via free radical polymerization.

[0072] In some embodiments, the polymer particle core of the present disclosure can be prepared by a dispersion polymerization method, in which a homogeneous solution is formed, wherein monomers, initiators, and stabilizers are combined in a solvent or solvent mixture. As the polymerization proceeds, the initially formed polymer precipitates out of the homogeneous solution to form precipitated nuclei. The formed precipitated nuclei still carry reactive sites, such as free radicals, which allow them to keep growing by continuously capturing and incorporating monomers and / or oligomers from the solution.

[0073] In an exemplary method based on free radical polymerization, one or more solvents and one or more stabilizers are purged with nitrogen to remove dissolved oxygen. Then, one or more monomers (including at least one multifunctional monomer) and a free radical polymerization initiator are added. Usually, under stirring, free radical polymerization is initiated by increasing the temperature for several hours. Based on the desired particle diameter, additional free radical polymerization initiators and additional monomers can be added to the reaction mixture to allow the particles to further grow to the desired size. After the reaction, the particles can be thoroughly washed and dried under vacuum.

[0074] Any free radical initiator compatible with the organic phase can be used alone or in a mixture of such free radical initiators. In a specific embodiment, the free radical initiator can be thermally activated or photoactivated. In a specific embodiment, the free radical initiator is a peroxide, peracetic acid, persulfate, azo initiator or a mixture thereof.

[0075] In the case where the initiator is a thermal initiator, the resulting solution can then be heated to an elevated temperature with stirring to activate the thermal initiator and maintained at the elevated temperature until polymerization is complete. In the case where the initiator is a photoinitiator, the resulting solution can then be irradiated with light of a suitable wavelength with stirring to activate the photoinitiator and maintained until polymerization is complete. Suitable organic monomers for the organic phase are as described above.

[0076] Solvent systems used to form polymer particle cores include methanol, ethanol, isopropanol, 2-methoxyethanol, water, acetonitrile, p-xylene, and toluene.

[0077] Stabilizers that can be used to form the polymer particle core include, for example, polyvinyl pyrrolidone (PVP); nonionic surfactants, including alkylphenol ethoxylates (e.g., Triton™ N-57, available from Dow Chemical); polyvinyl alcohol (PVA), such as Selvol TM Polyvinyl alcohol solution (available from Sekisui Special Chemicals); modified celluloses, including alkyl-modified celluloses such as methyl cellulose (e.g. Methocel TM , available from DuPont); and a hydrophobically modified cellulose hydroxyethyl cellulose stabilizer, such as Natrosol TM cetyl modified hydroxyethyl cellulose (available from Ashland); and ionic surfactants, including sodium alkyl sulfates, such as sodium dodecyl sulfate (SDS) and sodium oleyl sulfate, and the like.

[0078] In a specific embodiment of the nonporous polymer particle core formation, the monomers are a combination of DVB and styrene, the initiator is 2,2'-azobis(2-methylpropionitrile) (AIBN), the solvent system is a combination of reagent alcohol and p-xylene, and the stabilizer is polyvinylpyrrolidone (PVP 40).

[0079] Once formed, the organic polymer core may contain surface moieties from which further polymerization may be carried out. For example, nonporous polymer particle cores formed by free radical polymerization typically contain residual free radical polymerizable unsaturated surface moieties (e.g., ethylenyl moieties, vinyl moieties, methacryloxy moieties, or acryloxy moieties, etc.) from which further core growth may be carried out. Such further polymerization may be used to increase the size of a given batch of polymer particle cores by adding additional thickness of nonporous organic polymer to previously formed nonporous polymer particle cores.

[0080] In a specific embodiment of nonporous polymer particle core growth, the monomer is DVB, the solvent is reagent alcohol, and the stabilizer is polyvinylpyrrolidone (PVP 40).

[0081] Surface modified nonporous polymer core

[0082] In some embodiments, the present application relates to having a modified surface (e.g., 120, Figure 1 ) surface porous polymer particles. In some embodiments, the modified surface of the nonporous polymer particle core can form a covalent bond or an electrostatic bond with a subsequently applied nonporous organic-inorganic hybrid material. In certain embodiments, the modified surface of the nonporous polymer core is a silyl-modified surface. The silyl-modified surface comprises a first functional group and a second functional group. For example, the first functional group is a reactive silane (e.g., an alkoxy group), and the second functional group is an organic polymerizable group (e.g., a vinyl group).

[0083] In some embodiments, the modified surface of the nonporous polymer particle core may have a thickness in the range of 1 nm to 300 nm, for example, any thickness in the range of 1 nm to 3 nm to 10 nm to 30 nm to 100 nm to 300 nm (i.e., in a range between any two of the foregoing values).

[0084] In some embodiments, the modified surface includes a surface polymer, which may include a functional group covalently bonded or electrostatically bonded to an organic-inorganic hybrid nonporous shell. Examples of functional groups electrostatically bonded to an organic-inorganic hybrid nonporous shell include amide functional groups and amine functional groups. In this regard, the organic-inorganic hybrid nonporous material described herein is weakly acidic in nature, and therefore tends to be deprotonated and negatively charged, while the amide functional group or amine functional group described herein is alkaline in nature, and therefore tends to be protonated and positively charged. Examples of functional groups covalently bonded to an organic-inorganic hybrid nonporous shell include organosilane functional groups and organometallic functional groups, such as organotitanium functional groups and organozirconium functional groups. As used herein, an organosilane functional group is a functional group having at least one Si-C bond. Similarly, an organotitanium functional group is a functional group having at least one Ti-C bond, and an organozirconium functional group is a functional group having at least one Zr-C bond.

[0085] In some embodiments, the modified surface includes a surface polymer that may include monomer residues covalently or electrostatically bonded to the organic-inorganic hybrid nonporous shell. Examples of monomer residues electrostatically bonded to the organic-inorganic hybrid nonporous shell include amide monomer residues and amine monomer residues. Examples of monomer residues covalently bonded to the organic-inorganic hybrid nonporous shell include organosilane monomer residues, organotitanium monomer residues, and organozirconium monomer residues. As used herein, an organosilane monomer residue is a monomer residue having at least one Si-C bond, an organotitanium monomer residue is a monomer residue having at least one Ti-C bond, and an organozirconium monomer residue is a monomer residue having at least one Zr-C bond.

[0086] The surface polymer may comprise, for example, polymer chains grafted onto a nonporous polymer core.

[0087] The surface polymer may comprise, for example, a cross-linked polymer network formed on a non-porous polymer particle core.

[0088] The surface polymers can be prepared by a number of methods and mechanisms including, but not limited to, chain addition and stepwise condensation methods, free radical, anionic, cationic, ring opening, group transfer, metathesis, and photochemical mechanisms. In particularly advantageous embodiments, the nonporous organic polymer core is prepared via free radical polymerization.

[0089] As mentioned above, the polymer particle core may contain surface moieties from which further polymerization may be carried out. For example, organic polymer cores formed by free radical polymerization typically contain residual free radical polymerizable unsaturated surface moieties (e.g., ethylenyl moieties, vinyl moieties, methacryloxy moieties, acryloxy moieties, etc.) from which polymerization of surface polymers may be carried out. The polymer chains may be derived from monofunctional monomers. The crosslinked polymer network may be formed from multifunctional monomers. In addition to multifunctional monomers, monofunctional monomers may also be included in such crosslinked polymer networks.

[0090] As described above, surface polymers include those comprising amide monomer residues. Examples of amide monomer residues include amide monomer residues having the formula: wherein n is an integer from 1 to 3 (i.e., N-vinylpyrrolidone, N-vinyl-2-piperidone, or N-vinylcaprolactam). Examples of amide monomer residues also include those having the formula An amide monomer residue, wherein R1 is selected from C1-C6 alkylene, C2-C6 alkenylene, C2-C6 alkynylene, C6-C18 arylene, and wherein R2 is selected from H, C1-C6 alkylene, C2-C6 alkenylene, C2-C6 alkynylene, C6-C18 arylene.

[0091] As also described above, surface polymers include those comprising amine monomer residues. Examples of amine monomer residues include aminoalkyl acrylates, aminoalkyl methacrylates, dialkylaminoalkyl acrylates, or dialkylaminoalkyl methacrylates, including amino-C1-C4-alkyl acrylates, amino-C1-C4-alkyl methacrylates, di-C1-C4-alkylamino-C1-C4-alkyl acrylates, di-C1-C4-alkylamino-C1-C4-alkyl methacrylates, such as 2-aminoethyl acrylate, 2-aminoethyl methacrylate, 2-(N,N-dimethylamino)ethyl acrylate, 2-(N,N-dimethylamino)ethyl methacrylate, 2-(N,N-diethylamino)ethyl methacrylate, or 2-diisopropylaminoethyl methacrylate.

[0092] As further described above, examples of surface polymers also include those comprising silane monomer residues electrostatically bonded to the organic-inorganic hybrid nonporous material. In some embodiments, the surface polymer comprises residues of one or more free radically polymerizable organosilane monomers.

[0093] Specific examples of free radical polymerizable organosilane monomers include unsaturated organosilane monomers (e.g., unsaturated organoalkoxysilane monomers, unsaturated organochlorosilane monomers, etc.), such as alkenyl or alkynyl functionalized organosilane monomers (e.g., alkenyl or alkynyl functionalized organoalkoxysilane monomers, alkenyl or alkynyl functionalized organochlorosilane monomers, etc.). Specific alkenyl functionalized organoalkoxysilane monomers include those having vinyl groups, methacryloxy groups, and acryloxy groups. Specific examples include 3-(trimethoxysilyl)propyl methacrylate (also known as 3-methacryloxypropyltrimethoxysilane or MAPTMOS), methacryloxypropyltriethoxysilane, methacryloxypropyltrichlorosilane, vinyltriethoxysilane (VTES), vinyltrimethoxysilane, N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, (3-acryloxypropyl)trimethoxysilane, O-(methacryloxyethyl)-N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, -(triethoxysilylpropyl)urethane, N-(3-methacryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropylmethyldimethoxysilane, methacryloxypropyltri(methoxyethoxy)silane, 3-(N-phenylvinylmethyl-2-aminoethylamino)propyltrimethoxysilane hydrochloride, etc.

[0094] In a specific embodiment of the method for forming a surface-modified nonporous organic polymer core, an organosilane polymer, specifically a poly(styryl-C1-C4-alkyl-tri-C1-C4-alkoxysilane), is formed by copolymerizing a styryl-C1-C4-alkyl-tri-C1-C4-alkoxysilane monomer (wherein R is a C1-C4 alkyl) with a residual vinyl group (e.g., a residue of divinylbenzene) on the nonporous organic polymer core. Examples of styryl organosilane monomers include styrylethyltrimethoxysilane and styryltrimethoxysilane.

[0095] Nonporous organic-inorganic hybrid materials

[0096] As previously mentioned, the present disclosure relates to core-shell particles in which a nonporous organic-inorganic hybrid material (e.g. Figure 1 130) is in contact with the modified surface of the non-porous polymer core.

[0097] In some embodiments, the nonporous organic-inorganic hybrid material may have a thickness in the range of, for example, 10 nm to 200 nm, typically 25 nm to 100 nm. In some embodiments, the nonporous organic-inorganic hybrid material may have a pore volume of, for example, less than 0.1 cc / g (e.g., 0.05 cc / g), typically less than 0.02 cc / g.

[0098] "Organic-inorganic hybrid" materials include inorganic-based structures in which organic functional groups are integrated with both the internal or "framework" inorganic structure and the surface of the hybrid material. The inorganic portion of the hybrid material can be, for example, silicon dioxide, aluminum oxide, titanium, cerium or zirconium or their oxides, or a ceramic material. Exemplary hybrid materials are shown in U.S. Patents 4,017,528, 6,528,167, 6,686,035, 7,175,913 and 7,919,177, the disclosures of which are hereby incorporated in their entirety.

[0099] In some embodiments, the nonporous organic-inorganic hybrid material may include a silicon-based organic-inorganic hybrid material, which includes a hybrid region, wherein the silicon-based nonporous organic-inorganic hybrid material includes a silicon atom having one or more silicon-oxygen bonds and one or more silicon-carbon bonds. In some cases, the hybrid region may include a substituted or unsubstituted alkylene, alkenylene, alkynylene or arylene moiety bridging two or more silicon atoms. For example, the hybrid region may include a substituted or unsubstituted C1-C18 alkylene, C2-C18 alkenylene, C2-C18 alkynylene or C6-C18 arylene moiety bridging two or more silicon atoms. In some embodiments, the hybrid region may include a substituted or unsubstituted C1-C6 alkylene moiety bridging two or more silicon atoms, including a methylene, dimethylene or trimethylene moiety bridging two silicon atoms. In some embodiments, the hybrid region may include a ≡Si-(CH2)n-Si≡ portion, where n is an integer and may be equal to 1, 2, 3, 4 or greater. In some embodiments, the nonporous organic-inorganic hybrid material may include a silicon-based nonporous organic-inorganic hybrid material that further includes an inorganic region in which the material includes silicon atoms having four silicon-oxygen bonds in addition to a hybrid region in which the material includes silicon atoms having one or more silicon-oxygen bonds and one or more silicon-carbon bonds.

[0100] In various embodiments, the nonporous organic-inorganic hybrid material can be formed by hydrolytic condensation of one or more organosilane compounds on the modified surface of a nonporous organic polymer core (such as those described above). As used herein, an organosilane compound is a silane compound having at least one Si-C bond.

[0101] The organosilane compound may include, for example, (a) one or more organosilane compounds of the formula SiZ1Z2Z3Z4, wherein Z1, Z2, Z3 and Z4 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, wherein at least one of Z1, Z2, Z3 and Z4 is C1-C4 alkyl, examples of which include alkyl-trialkoxysilanes, such as C1-C4-alkyl-tri-C1-C4-alkoxysilanes, including methyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane or ethyltriethoxysilane, and dialkyl-dialkoxysilanes, such as C1-C4-dialkyl-di-C1-C4-alkoxysilanes, such as dimethyldiethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane or diethyldiethoxysilane. and many other possibilities, and / or (b) one or more organosilane compounds of the formula Z1Z2Z3Si—R—SiZ4Z5Z6, wherein Z1, Z2 and Z3 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, but at most two of Z1, Z2 and Z3 can be C1-C4 alkyl, wherein Z4, Z5 and Z6 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, but at most two of Z4, Z5 and Z6 can be C1-C4 alkyl, and wherein R is an organic group, for example selected from C1-C18 alkylene, C2-C18 alkenylene, C2-C18 alkynylene or C6-C18 arylene, typically C1-C4 alkylene, typically C1-C6 alkylene. Examples of compounds of the formula Z1Z2Z3Si—R—SiZ4Z5Z6 include bis(trialkoxysilyl)alkanes, for example, bis(tri-C1-C4-alkoxysilyl)C1-C4-alkanes such as bis(trimethoxysilyl)methane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)methane and bis(triethoxysilyl)ethane as well as many other possibilities.

[0102] In some embodiments, one or more additional non-organosilane compounds can be hydrolyzed and condensed with one or more organosilane compounds. Such compounds include silane compounds of formula SiZ1Z2Z3Z4, wherein Z1, Z2, Z3 and Z4 are independently selected from Cl, Br, I, C1-C4 alkoxy and C1-C4 alkylamino. In certain embodiments, the additional silane compound is tetra-C1-C4-alkoxysilane, such as tetramethoxysilane or tetraethoxysilane.

[0103] In some embodiments, the nonporous organic-inorganic hybrid material can be formed by hydrolytic condensation of the following substances on the modified surface of the nonporous organic polymer core as described above: (a) one or more alkoxysilanes, such as tetraalkoxysilanes (e.g., tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), etc.), and (b) one or more organosilanes, for example, selected from bis(trialkoxysilyl)alkanes (e.g., bis(trimethoxysilyl)methane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)methane, bis(triethoxysilyl)ethane (BTEE), etc.) and / or alkyltrialkoxysilanes (e.g., methyltrimethoxysilane, methyltriethoxysilane (MTOS), ethyltriethoxysilane, etc.). In the case where the plurality of silane compounds includes one or more bis(trialkoxysilyl)alkanes, an alkyl-bridged nonporous organic-inorganic hybrid material is prepared, which can provide various advantages over conventional silica-based materials, including chemical and mechanical stability. When BTEE is used as a monomer, the resulting material is an ethylene bridged hybrid (BEH) material. A specific BEH material can be formed by the hydrolytic condensation of TEOS and BTEE.

[0104] In some embodiments, a plurality of silane compounds as described above (e.g., a plurality of silane compounds comprising one or more organosilanes and one or more tetraalkoxysilanes) are partially condensed to form a polyalkoxyorganosiloxane oligomer, which is then hydrolyzed and condensed onto the surface-modified nonporous organic polymer core. For example, BTEE and TEOS may be partially condensed to form a polyethoxyorganosiloxane oligomer (PEOS), which is hydrolyzed and condensed onto the modified surface of the nonporous organic polymer core.

[0105] In various embodiments, the nonporous organic-inorganic hybrid material can be formed by producing (usually in a series of steps) a reaction mixture comprising the following components: a nonporous organic polymer core having a modified surface, ethanol, one or more silanes (including one or more organosilanes as described above (e.g., TEOS and BTEE, or PEOS)), water, and a basic or acidic catalyst, the catalyst being used to promote the hydrolysis and condensation of the silanes on the modified surface of the nonporous organic polymer core of the nonporous organic-inorganic hybrid material. In some embodiments, the hydrolysis is carried out at room temperature. In some embodiments, the mixture can be heated to drive the hydrolysis reaction to completion. In some embodiments, the mixture is stirred. After the organic-inorganic hybrid nonporous material is formed, the resulting particles can be washed and dried.

[0106] In other embodiments, nonporous organic-inorganic hybrid materials can be formed by the interaction between a template surfactant (e.g., and an ionic surfactant such as hexadecyltrimethylammonium bromide (CTAB) or trioctylmethylammonium bromide (TOMB)) and one or more silanes (including one or more organosilanes as described above (e.g., TEOS and BTEE, or PEOS)) during the continuous addition of silanes, alkaline catalysts, and template surfactants to a surface-modified nonporous organic polymer core. The process results in continuous silane hydrolysis and condensation of organic-inorganic hybrid reaction products on the core. The reaction can be carried out at room temperature or elevated temperature.

[0107] One or more organosilanes (e.g., TEOS and BTEE, or PEOS) as described above can be hydrolyzed in the presence of a modified surface of a nonporous (NP) organic polymer core having a surface polymer comprising monomer residues of an amide monomer and / or a silane monomer, such that the hydrolyzed organosilanes form a nonporous organic-inorganic hybrid material on the modified surface of the core.

[0108] Porous organic-inorganic hybrid materials

[0109] As previously mentioned, the present disclosure relates to core-shell particles in which a porous organic-inorganic hybrid shell material is in contact with a nonporous organic-inorganic hybrid material, which is in contact with a modified surface of a nonporous polymer particle core. Figure 1 As shown in the core-shell particle 100, a nonporous organic-inorganic hybrid material 130 is deposited or grown on the modified surface 120 of the nonporous polymer particle core 110, and a porous organic-inorganic hybrid shell material 150 is deposited or grown on the nonporous organic-inorganic hybrid material 130. The pores 106 extend within the porous organic-inorganic hybrid shell material 150. Thus, the particle 100 has a nonporous central portion (e.g., core 110, nonporous organic-inorganic hybrid material 130) and a porous shell portion.

[0110] The porous organic-inorganic hybrid shell material can have a pore volume of 0.1cc / g shell material or greater (e.g., 0.2cc / g), and preferably greater than 0.65cc / g shell material. In various embodiments, the pore volume of the porous organic-inorganic hybrid shell material is substantially greater than 0.15cc / g shell material, such as a pore volume in the range of 0.2cc / g to 1.5cc / g shell material, preferably in the range of 0.4cc / g to 0.75cc / g shell material. Therefore, the hybrid material of the shell is porous compared to the hybrid material in contact with the modified surface of the polymer core.

[0111] In some embodiments, the thickness of the porous organic-inorganic hybrid shell material may be, for example, in the range of 0.1 micron to 4 microns, typically in the range of 0.1 micron to 2 microns, more typically in the range of 0.1 micron to 1.2 microns. In some embodiments, the ratio of the diameter of the core to the diameter of the entire particle may be, for example, in the range of 0.3:1 to 0.95:1, more typically 0.65:1 to 0.8:0.9.

[0112] In some embodiments, the porous organic-inorganic hybrid shell material may have or smaller or larger apertures, e.g. to to to to to to Any aperture within the range.

[0113] "Organic-inorganic hybrid" materials include inorganic-based structures in which organic functional groups are integrated with both the internal or "framework" inorganic structure and the surface of the hybrid material. The inorganic portion of the hybrid material can be, for example, silicon dioxide, aluminum oxide, titanium, cerium or zirconium or their oxides, or a ceramic material. Exemplary hybrid materials are shown in U.S. Patents 4,017,528, 6,528,167, 6,686,035, 7,175,913 and 7,919,177, the disclosures of which are hereby incorporated in their entirety.

[0114] In some embodiments, the materials forming the nonporous organic-inorganic hybrid material and the porous organic-inorganic hybrid shell material can be chemically identical or similar; the difference or distinction between the two materials is the amount of porosity. The porous organic-inorganic hybrid shell material has a pore volume greater than 0.1 cc / g in the entire shell material, preferably greater than 0.15 cc / g in the entire shell material; while the nonporous organic-inorganic hybrid material has a porosity of typically 0.05 cc / g or less.

[0115] In some embodiments, the organic-inorganic hybrid shell material may include a silicon-based organic-inorganic hybrid material comprising a hybrid region, wherein the material comprises silicon atoms having one or more silicon-oxygen bonds and one or more silicon-carbon bonds. In some cases, the hybrid region may include a substituted or unsubstituted alkylene, alkenylene, alkynylene, or arylene moiety bridging two or more silicon atoms. For example, the hybrid region may include a substituted or unsubstituted C 2- or C 3-alkylene moiety bridging two or more silicon atoms. 1 -C 18 Alkylene, C 2 -C 18 Alkenylene, C 2-C 18 Alkyne or C 6 -C 18 In certain embodiments, the hybrid region may include substituted or unsubstituted C 2- or C 3-alkylene groups bridging two or more silicon atoms. 1 -C 6 Alkylene moieties include methylene, dimethylene, or trimethylene moieties bridging two silicon atoms. In certain embodiments, the hybrid region may include ≡Si-(CH 2 ) n -Si≡ moiety, where n is an integer and can be equal to 1, 2, 3, 4 or greater. In some embodiments, the organic-inorganic hybrid shell can include a silicon-based organic-inorganic hybrid material that includes an inorganic region in which the material includes silicon atoms having four silicon-oxygen bonds in addition to a hybrid region in which the material includes silicon atoms having one or more silicon-oxygen bonds and one or more silicon-carbon bonds.

[0116] In some embodiments, the porous organic-inorganic hybrid shell material may comprise an organic-inorganic hybrid material of Formula I:

[0117] (SiO 2 ) d / [R 2 ((R) p (R 1 ) q SiO t ) m ](I)

[0118] in,

[0119] R and R 1 Each independently is C 1 -C 18 Alkoxy, C 1 -C 18 Alkyl, C 1 -C 18 Alkyl, C 2 -C 18 Alkenyl, C 2 -C 18 Alkynyl, C 3 -C 18 Cycloalkyl, C 1 -C 18 Heterocycloalkyl, C 5 -C 18 Aryl, C 5 -C 18 Aryloxy, or C 1 -C 18 heteroaryl;

[0120] R2 is C 1 -C 18 alkyl, C 2 -C 18 alkenyl, C 2 -C 18 alkynyl, C 3 -C 18 cycloalkyl, C 1 -C 18 heterocycloalkyl, C 5 -C 18 aryl, C 1 -C 18 heteroaryl; or is absent; wherein each R 2 is connected to two or more silicon atoms;

[0121] p and q are each independently from 0.0 to 3.0;

[0122] t is 0.5, 1.0, or 1.5;

[0123] d is from 0 to about 30;

[0124] m is an integer from 1 to 20; wherein R, R 1 and R 2 are optionally substituted;

[0125] provided that:

[0126] (1) when R 2 is absent, m = 1, and when 0 < p + q ≤ 3, and

[0127] (2) when R 2 is present, m = 2 - 20, and when p + q ≤ 2, 2.

[0128] In some embodiments, the organic-inorganic hybrid shell may comprise an organic-inorganic hybrid material of formula II:

[0129] (SiO 2 ) d / [(R) p (R 1 ) q SiO t (II)

[0130] wherein,

[0131] R and R 1 are each independently C 1 -C 18 alkoxy, C 1 -C 18 alkyl, C 1 -C18 Alkyl, C 2 -C 18 Alkenyl, C 2 -C 18 Alkynyl, C 3 -C 18 Cycloalkyl, C 1 -C 18 Heterocycloalkyl, C 5 -C 18 Aryl, C 5 -C 18 Aryloxy, or C 1 -C 18 heteroaryl;

[0132] d is 0 to about 30;

[0133] p and q are each independently 0.0 to 3.0, with the proviso that when p+q=1, then t=1.5; when p+q=2, then t=1; or when p+q=3, then t=0.5.

[0134] In some embodiments, the organic-inorganic hybrid shell may comprise an organic-inorganic hybrid material of Formula III:

[0135] (SiO 2 ) d / [R 2 ((R 1 ) r SiO t ) m ] (III)

[0136] in,

[0137] R 1 C 1 -C 18 Alkoxy, C 1 -C 18 Alkyl, C 1 -C 18 Alkyl, C 2 -C 18 Alkenyl, C 2 -C 18 Alkynyl, C 3 -C 18 Cycloalkyl, C 1 -C 18 Heterocycloalkyl, C 5 -C 18 Aryl, C 5 -C 18 Aryloxy, or C 1 -C 18 Heteroaryl; R 2 C 1 -C18 Alkyl, C 2 -C 18 Alkenyl, C 2 -C 18 Alkynyl, C 3 -C 18 Cycloalkyl, C 1 -C 18 Heterocycloalkyl, C 5 -C 18 Aryl, C 1 -C 18 heteroaryl; or absent; wherein each R 2 connected to two or more silicon atoms;

[0138] d is 0 to about 30;

[0139] r is 0, 1 or 2, provided that when r = 0, then t = 1.5; or when r = 1, then t = 1; or when r = 2, then t = 0.5; and

[0140] m is an integer of 1-20.

[0141] In some embodiments, the organic-inorganic hybrid shell material may comprise an organic-inorganic hybrid material of Formula IV:

[0142] (A)x(B)y(C)z (IV),

[0143] wherein the order of repeating units A, B and C may be random, block or a combination of random and block; A is an organic repeating unit covalently bonded to one or more repeating units A or B via an organic bond; B is an organosiloxane repeating unit bonded to one or more repeating units B or C via an inorganic siloxane bond, and may be further bonded to one or more repeating units A or B via an organic bond; C is an inorganic repeating unit bonded to one or more repeating units B or C via an inorganic bond; and x and y are positive numbers, and z is a non-negative number, wherein x+y+z=1. In certain embodiments, when z=0, then 0.002≤x / y≤210, and when z≠0, then 0.0003≤y / z≤500 and 0.002≤x / (y+z)≤210.

[0144] In some embodiments, the organic-inorganic hybrid shell material may comprise an organic-inorganic material of Formula V:

[0145] (A)x(B)y(B*)y*(C)z (V),

[0146] wherein the order of repeating units A, B, B* and C can be random, block or a combination of random and block;

[0147] A is an organic repeating unit, which is covalently bonded to one or more repeating units A or B via an organic bond; B is an organosiloxane repeating unit, which is bonded to one or more repeating units via an inorganic siloxane bond.

[0148] B or B* or C, and may be further bonded to one or more repeating units A or B via an organic bond;

[0149] B* is an organosiloxane repeating unit that is bonded to one or more repeating units B or B* or C via an inorganic siloxane bond, wherein B* is an organosiloxane repeating unit that has no reactive (i.e., polymerizable) organic component and may also have a protected functional group that may be deprotected after polymerization; C is an inorganic repeating unit that is bonded to one or more repeating units B or B* or C via an inorganic bond; and

[0150] x, y, and y* are positive numbers, and z is a non-negative number, wherein x+y+z = 1. In certain embodiments, when z = 0, then 0.002≤x / (y+y*)≤210, and when z≠0, then 0.0003≤(y+y*) / z≤500 and 0.002≤x / (y+y*+z)≤210.

[0151] In various embodiments, the organic-inorganic hybrid material can be formed by hydrolytic condensation of one or more organosilane compounds on a surface modified nonporous organic polymer core such as those described above. As used herein, an organosilane compound is a silane compound having at least one Si-C bond.

[0152] The organosilane compound may comprise, for example, (a) one or more of the formula SiZ 1 Z 2 Z 3 Z 4 An organosilane compound, wherein Z 1 , Z 2 , Z 3 and Z 4 Independently selected from Cl, Br, I, C 1 -C 4 Alkoxy, C 1 -C 4 Alkylamino and C 1 -C 4 Alkyl, where Z 1 , Z 2 , Z 3 and Z 4 At least one of them is C 1 -C 4 Alkyl groups, examples of which include alkyl-trialkoxysilanes such as C 1 -C 4 -alkyl-tri-C 1 -C4 - alkoxysilanes, including methyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane or ethyltriethoxysilane, and dialkyl-dialkoxysilanes, such as C 1 -C 4 -dialkyl-di-C 1 -C 4 - alkoxysilanes such as dimethyldiethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane or diethyldiethoxysilane as well as many other possibilities, and / or (b) one or more compounds of the formula Z 1 Z 2 Z 3 Si—R—SiZ 4 Z 5 Z 6 An organosilane compound, wherein Z 1 , Z 2 and Z 3 Independently selected from Cl, Br, I, C 1 -C 4 Alkoxy, C 1 -C 4 Alkylamino and C 1 -C 4 Alkyl, but Z 1 , Z 2 and Z 3 At most two of them can be C 1 -C 4 Alkyl, where Z 4 , Z 5 and Z 6 Independently selected from Cl, Br, I, C 1 -C 4 Alkoxy, C 1 -C 4 Alkylamino and C 1 -C 4 Alkyl, but Z 4 , Z 5 and Z 6 At most two of them can be C 1 -C 4 alkyl, and wherein R is an organic group, for example selected from C 1 -C 18 Alkylene, C 2 -C 18 Alkenylene, C 2 -C 18 Alkyne or C 6 -C 18 Arylene, usually C 1 -C 4 Alkylene, usually C 1 -C6 Alkylene. Formula Z 1 Z 2 Z 3 Si—R—SiZ 4 Z 5 Z 6 Examples of compounds include bis(trialkoxysilyl)alkanes, for example, bis(tri-C 1 -C 4 -alkoxysilyl)C 1 -C 4 - Alkanes such as bis(trimethoxysilyl)methane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)methane and bis(triethoxysilyl)ethane as well as many other possibilities.

[0153] In some embodiments, one or more additional non-organosilane compounds may be hydrolyzed and condensed with one or more organosilane compounds. Such compounds include those of the formula SiZ 1 Z 2 Z 3 Z 4 Silane compounds, wherein Z 1 , Z 2 , Z 3 and Z 4 Independently selected from Cl, Br, I, C 1 -C 4 Alkoxy and C 1 -C 4 In certain embodiments, the additional silane compound is a tetra-C 1 -C 4 - Alkoxysilanes, such as tetramethoxysilane or tetraethoxysilane.

[0154] In some embodiments, the porous organic-inorganic hybrid shell material can be formed by hydrolyzing and condensing the following substances on the non-porous organic-inorganic hybrid material as described above: (a) one or more alkoxysilanes, such as tetraalkoxysilanes (e.g., tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), etc.), and (b) one or more organosilanes, for example, selected from bis(trialkoxysilyl)alkanes (e.g., bis(trimethoxysilyl)methane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)methane, bis(triethoxysilyl)ethane (BTEE), etc.) and / or alkyltrialkoxysilanes (e.g., methyltrimethoxysilane, methyltriethoxysilane (MTOS), ethyltriethoxysilane, etc.). In the case where the plurality of silane compounds includes one or more bis(trialkoxysilyl)alkanes, an alkyl-bridged organic-inorganic hybrid material is prepared, which can provide various advantages over conventional silica-based materials, including chemical and mechanical stability. When BTEE is used as a monomer, the resulting material is an ethylene bridged hybrid (BEH) material. A specific BEH material can be formed by the hydrolytic condensation of TEOS and BTEE.

[0155] In some embodiments, a plurality of silane compounds as described above (e.g., a plurality of silane compounds comprising one or more organosilanes and one or more tetraalkoxysilanes) are partially condensed to form a polyalkoxyorganosiloxane oligomer, which is then hydrolyzed and condensed onto the nonporous organic-inorganic hybrid material. For example, BTEE and TEOS may be partially condensed to form a polyethoxyorganosiloxane oligomer (PEOS), which is hydrolyzed and condensed onto the nonporous organic-inorganic hybrid material.

[0156] In various embodiments, the porous organic-inorganic hybrid shell material can be formed by producing (usually in a series of steps) a reaction mixture comprising the following components: a nonporous organic polymer core having a modified surface and a nonporous organic-inorganic hybrid material in contact with the modified surface (i.e., an initial nonporous particle), ethanol, one or more pore formers, one or more silanes (including one or more organosilanes as described above (e.g., TEOS and BTEE, or PEOS)), water, and a basic or acidic catalyst, the catalyst being used to promote the hydrolysis and condensation of the silanes of the organic-inorganic hybrid material on the outermost surface of the initial nonporous particles. In some embodiments, the hydrolysis is carried out at room temperature. In some embodiments, the mixture can be heated to drive the hydrolysis reaction to completion. In some embodiments, the mixture is stirred. After the organic-inorganic hybrid shell material is formed, the resulting particles can be washed and dried. Typically, porosity is introduced by extracting, degrading, or evaporating the pore former.

[0157] Examples of pore formers include the following: water-immiscible organic solvents such as toluene; nonionic surfactants including aromatic polyoxyethylene surfactants such as Triton TM Surfactants; polyoxyethylene-polyoxypropylene block copolymers, such as Pluronic TM Surfactants; and ionic surfactants, such as cetyltrimethylammonium bromide (CTAB) and trioctylmethylammonium bromide (TMAB); polyphenol compounds, such as tannic acid; and organic polymers, such as polystyrene.

[0158] Examples of the basic catalyst include hydroxide salts such as potassium hydroxide, sodium hydroxide, or ammonium hydroxide; and amines such as octylamine, N,N-dimethylhexadecylamine, and dodecylamine.

[0159] In other embodiments, the porous organic-inorganic hybrid shell material can be formed by the interaction between the template surfactant (e.g., and an ionic surfactant such as hexadecyltrimethylammonium bromide (CTAB) or trioctylmethylammonium bromide (TOMB)) and one or more silanes (including one or more organosilanes as described above (e.g., TEOS and BTEE, or PEOS)) during the continuous addition of the silane, the alkaline catalyst, and the template surfactant to the surface modified non-porous organic polymer core. The method results in continuous silane hydrolysis and condensation of the organic-inorganic hybrid reaction product on the core. The reaction can be carried out at room temperature or at an elevated temperature. The porous organic-inorganic hybrid shell material is formed after the template surfactant is subsequently removed.

[0160] In some embodiments, one or more organosilanes (e.g., TEOS and BTEE, or PEOS) as described above can be hydrolyzed in the presence of a pore former and a starting non-porous particle having a surface polymer comprising monomer residues of an amide monomer and / or a silane monomer, such that the hydrolyzed organosilanes form an organic-inorganic hybrid material on the core. After removing the pore former, a porous organic-inorganic hybrid shell material is formed.

[0161] Bonding material

[0162] As previously mentioned, in some embodiments, the core-shell particles as disclosed herein may further include a binding material that modifies one or more portions of the core-shell particles. For example, the modified surface, non-porous organic-inorganic hybrid material, and / or porous organic-inorganic hybrid shell material may be modified with a binding material. The modification may be an intrinsic modification (i.e., the binding material is included when a portion of the particle is deposited or grown), a surface modification (i.e., the modification is applied to the exposed surface of the particle), or a combination thereof. Figure 2As shown, in the embodiment (particle 200), the porous organic-inorganic hybrid shell material 250 is surface-modified with a binding material 240; a layer or region extending from the porous organic-inorganic hybrid shell material 250 is formed. The porous organic-inorganic hybrid shell material 250 is at least partially in contact with the non-porous organic-inorganic hybrid material 230. The non-porous organic-inorganic hybrid material 230 may not be in contact with the porous organic-inorganic hybrid shell material 250, wherein the pores 206 of the porous organic-inorganic hybrid shell material 250 extend to the surface of the non-porous organic-inorganic hybrid material 230. In the case where the non-porous organic-inorganic hybrid material 230 is not in contact with the porous organic-inorganic hybrid shell material 250, the non-porous organic-inorganic hybrid material 230 may also be surface-modified with a binding material 240. In some cases, the bonding material 240 is covalently or electrostatically bonded to the porous organic-inorganic hybrid shell material 250 and / or the non-porous organic-inorganic hybrid material 230. Figure 2 It can be seen that the modified surface 220 of the nonporous polymer core 210 is in contact with the nonporous organic-inorganic hybrid material 230, which is in contact with the porous organic-inorganic hybrid shell material 250. The bonding material 240 is in contact with the nonporous organic-inorganic hybrid material 230 (in the case where the nonporous organic-inorganic hybrid material 230 is not in contact with the porous organic-inorganic hybrid shell material 250, i.e., within the pores 206) and the porous organic-inorganic hybrid shell material 250.

[0163] In another embodiment (particle 300), and as Figure 3 As shown, the porous organic-inorganic hybrid shell material 350 is surface-modified with a binding material 340a. In addition, the non-porous organic-inorganic hybrid material 330 and the porous organic-inorganic hybrid shell material 350 are internally modified with a binding material 340b. That is, the binding material 340b is contained in at least a portion of the non-porous organic-inorganic hybrid material 330 and in the porous hybrid inorganic shell material 350. In some embodiments (not shown), the binding material 340b may be contained in the porous organic-inorganic hybrid shell material 350 and / or the non-porous organic-inorganic hybrid material 330 in a gradient form (i.e., the concentration of the binding material 340b varies with the thickness). The non-porous organic-inorganic hybrid material 330 (without contacting the porous organic-inorganic hybrid shell material 350) and the porous organic-inorganic hybrid shell material 350 are additionally surface-modified with a binding material 340a. From Figure 3 It can be seen that the nonporous organic-inorganic hybrid material 330 is in contact with the porous organic-inorganic hybrid shell material 350, and both the nonporous organic-inorganic hybrid material 330 and the porous organic-inorganic hybrid shell material 350 are in contact with (eg, have been modified by) the bonding materials 340a and 340b.

[0164] In some embodiments, the bonding material 340b included in the non-porous organic-inorganic hybrid material 330 and the porous organic-inorganic hybrid shell material 350 is the same as the bonding material 340a added after the growth of the porous organic-inorganic hybrid shell material 350. However, this need not be the case. In some embodiments, the bonding material 340b within the non-porous organic-inorganic hybrid material 330 is different from the bonding material 340a added after the growth of the porous organic-inorganic hybrid shell material 350 (e.g., supplying end caps on the outside of the shell material 330, or adding charges to create a charged surface).

[0165] In another embodiment (particle 400, such as Figure 4 In some embodiments (not shown), the porous organic-inorganic hybrid shell material 450 is surface-modified with a binding material 440a. In addition, the modified surface 420, the non-porous organic-inorganic hybrid material 430, and the porous organic-inorganic shell material 550 are internally modified with a binding material 440b. That is, the binding material 440b at least partially extends through the non-porous organic-inorganic hybrid shell material 450, the porous organic-inorganic hybrid material 430, and the modified surface 420. In some embodiments (not shown), the binding material 440b may be included in the porous organic-inorganic hybrid shell material 450 and / or the non-porous organic-inorganic hybrid material 430 in a gradient form (i.e., the concentration of the binding material 440b varies with the thickness of the particle 400). In Figure 4 In the particle 400 shown, the non-porous organic-inorganic hybrid material 430 (without contacting the porous organic-inorganic hybrid shell material 450) and the porous organic-inorganic hybrid shell material 450 are additionally surface-modified with a binding material 440a. Figure 4 As can be seen, modified surface 420 is in contact with nonporous organic-inorganic hybrid material 430, both of which are in contact with bonding material 440b. Nonporous organic-inorganic hybrid material 430 is also in contact with porous organic-inorganic hybrid shell material 450, both of which are in contact with (eg, have been modified with) bonding materials 440a and 440b.

[0166] In some embodiments, the binding material 440b extending within the modified surface 420 and the non-porous organic-inorganic hybrid material 430 is the same as the binding material 440a extending beyond the surface of the porous organic-inorganic hybrid material shell material 450. However, this need not be the case. In some embodiments, the binding material 440b extending within the modified surface 420 and the non-porous organic-inorganic hybrid material 430 is different from the binding material 440a extending beyond the surface of the porous organic-inorganic hybrid shell material 450 (e.g., end caps are provided outside the material 450, or charges are added to create a charged surface).

[0167] although Figure 4The particle 400 is shown with the binder material 440a added after the growth of the porous organic-inorganic hybrid shell material 450, but this need not be the case. Figure 5 As shown, in another embodiment, each of the modified surface 520, the nonporous organic-inorganic hybrid material 530, and the porous organic-inorganic hybrid shell material 550 of the particle 500 is internally modified with a binding material 540. That is, the binding material 540 is contained in at least a portion of the modified surface 520, in at least a portion of the nonporous organic-inorganic hybrid material 530, and in at least a portion of the porous organic-inorganic hybrid shell material 550. Figure 5 It can be seen that the modified surface 520 is in contact with the nonporous organic-inorganic hybrid material 530, which is also in contact with the porous organic-inorganic hybrid shell material 550, all of which are in contact with the binding material 540. In some embodiments, the binding material 540 is included in the nonporous organic-inorganic hybrid material 530 and / or in the porous organic-inorganic hybrid shell material 540 at varying concentrations (e.g., a gradient).

[0168] In some embodiments, the bonding material 540 included in the modified surface 520 and the nonporous organic-inorganic hybrid material 530 is the same as the bonding material 540 extending beyond the surface of the nonporous organic-inorganic hybrid material 530 (when not in contact with the porous organic-inorganic hybrid shell material 550, i.e., within the pores). However, this need not be the case. In some embodiments, the bonding material 540 extending within the modified surface 520 and the nonporous organic-inorganic hybrid material 530 is different from the bonding material 540 extending beyond the surface of the nonporous organic-inorganic hybrid material 530 (i.e., within the pores). For example, end caps are supplied externally to the material 530, or charges are added to create a charged surface, thereby changing or customizing the functional groups of the bonding material.

[0169] The bonding material can be functionalized (e.g., customized or adjusted) for a specific chromatographic separation or mode (obstacle chromatography, HDC, IP-RPLC, WAX). In some cases, at least a portion of the bonding material is a silane. The bonding material can be hydrophobic, hydrophilic, positively and / or negatively charged, or a combination thereof. In some cases, at least a portion of the bonding material can be an ionizable silane. The bonding material can include, but is not limited to, alkyl (e.g., C1 to C20), polyethylene glycol, hydrophilic polymers based on acrylamide and (meth)acrylate, polar groups containing nitrides, nitriles, hydroxyls, negatively and / or positively charged groups, amino, chlorine or alkoxysilanes, or a combination thereof.

[0170] In some embodiments, the bonding material can be uniformly incorporated into the core-shell particles, and the bonding material is deposited synchronously (i.e., intrinsically modified) and / or deposited after the modified surface, non-porous organic-inorganic hybrid material, and / or porous organic-inorganic hybrid shell material are deposited. The bonding material can be incorporated into the core-shell particles in a gradient form, and the bonding material is deposited after the modified surface, non-porous organic-inorganic hybrid material, and / or porous organic-inorganic hybrid shell material have begun but before the deposition of the specific area (e.g., 520, 530, 550) of the particle has ended. In some embodiments, the concentration or amount of the bonding material of the modified surface, non-porous organic-inorganic hybrid material, and / or porous organic-inorganic hybrid shell material can vary along the thickness of the surface and / or material. In some cases, the bonding material can be incorporated into the modified surface (e.g., silyl-modified surface) of the non-porous polymer particle core as a silane bonding. (See, for example, U.S. Patent Publication US2019 / 0322783). In some cases, at least a portion of the bonding material is a silane. The bonding material can be hydrophobic, hydrophilic, positively charged and / or negatively charged, or a combination thereof. In some cases, at least a portion of the bonding material can be an ionizable silane to form a functionalized surface.

[0171] As used herein, the term "gradient" refers to the composition of a particle as viewed from the center of the particle to the surface of the particle. In a gradient material, the composition of the material varies based on the order and concentration of monomers added in a predetermined pattern, such that there is a compositional variation along the radius of the particle, but no discrete shell of material is formed. For example, a material of a polymer particle may have a unique gradient composition across the radius from the particle core to the outermost surface, wherein the compositional gradient includes, but is not limited to, a hydrophobicity / hydrophilicity gradient, a crosslinking ratio gradient, a functional group gradient, a charge ratio gradient, a density gradient, or a combination thereof.

[0172] In some embodiments, divinylbenzene can be used to synthesize nonporous polymer particle cores. In some cases, the surface of the divinylbenzene particle core can be modified with styrene trimethoxysilane. In some cases, the modified divinylbenzene particle core surface can then be coated with an ethylene bridge hybrid (organic-inorganic hybrid) compound and combined to obtain alkaline stable particles for chromatographic biomolecule separation.

[0173] Potential advantages of the core-shell particles disclosed herein include improved mass transfer and increased efficiency relative to fully porous particles or fully non-porous particles, improved pH stability, and the ability to form arrays of particles and pore sizes. The core-shell particles can be used as chromatographic packing materials for separation of small molecules and large biologics.

[0174] Chromatographic device

[0175] In some aspects of the present disclosure, the core-shell particles described herein can be provided in a suitable chromatographic device. For this reason, the core-shell particles described herein can be provided together with a suitable shell. The core-shell particles and shell can be supplied independently, or the core-shell particles can be pre-packaged in the shell. The shell used according to the present disclosure generally includes a chamber for receiving and holding the core-shell particles. In various embodiments, the shell can be provided with an inlet and outlet leading to the chamber and leading out from the chamber.

[0176] Suitable materials of construction for the chromatography housing include inorganic materials, for example, metals such as stainless steel and ceramics such as glass, and synthetic polymeric materials such as polyethylene, polypropylene, polyetheretherketone (PEEK), and polytetrafluoroethylene, among others.

[0177] In certain embodiments, the chromatography housing can include one or more filters for retaining the core-shell particles in the housing. Exemplary filters can be in the form of, for example, a membrane, a mesh, a frit, or a spherical porous filter.

[0178] In certain embodiments, the chromatographic device is a chromatographic column.

[0179] The present disclosure also provides a kit comprising a core-shell particle, shell or device as described herein, and instructions for use. In one embodiment, the instructions are for a separation device, such as a chromatography column.

[0180] Chromatographic separation

[0181] In some aspects of the present disclosure, the core-shell particles of the present disclosure can be used for a variety of chromatographic separation methods. Therefore, the chromatographic device and chromatographic suit described herein can also be used for such methods. The example of the chromatographic separation method of the core-shell particles of the present invention can be used includes being used for high pressure liquid chromatography (HPLC) and ultra-high pressure liquid chromatography (UHPLC) in different modes. Those modes include but are not limited to affinity separation, hydrophilic interaction chromatography (HILIC) separation, normal phase separation, reverse phase separation, chiral separation, supercritical fluid chromatography SFC separation, perfusion separation, size exclusion chromatography (SEC) separation, ion exchange separation or multi-mode separation.

[0182] The core-shell particles, devices and kits disclosed herein can be used for chromatographic separations of substances such as small molecules, carbohydrates, antibodies, whole proteins, peptides and / or DNA.

[0183] Such chromatographic separation may include loading a sample onto the core-shell particles according to the present disclosure, and eluting the adsorbed species from the core-shell particles with a mobile phase.

[0184] Such chromatographic separations can be performed in conjunction with a variety of aqueous and / or organic mobile phases (i.e., in mobile phases containing water, organic solvents, or a combination of water and organic solvents) and in conjunction with a variety of mobile phase gradients (including gradients of solvent type, temperature, pH, salt concentration, or other parameters).

[0185] The following examples are provided to illustrate how to make composite particles and components thereof according to the present technology. These examples are for illustrative purposes only and should not be considered restrictive. When an amount, concentration or other value or parameter is given as a list of ranges, preferred ranges or upper preferred values ​​and lower preferred values, it should be understood that all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value are specifically disclosed, regardless of whether the range is disclosed separately. In the case of numerical ranges listed herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within the range. When limiting the range, the scope of the present technology is not intended to be limited to the specific value described.

[0186] Example 1: Non-porous poly(DVB80) particle core

[0187] In this embodiment, exemplary core-shell composite particles that are particularly advantageous in the separation of small molecules are manufactured. Specifically, various composite particles with different particle sizes are manufactured. Other methods and other materials can be used to manufacture the core-shell composite particles of the present technology.

[0188] The inhibitors in divinylbenzene (80%, technical grade) used in the particle synthesis were removed by passing the monomer through an alumina filter cartridge.

[0189] Primary particle synthesis In this particle synthesis experiment (sample 1A in Table 1 below), 65.1 grams of PVP-40, 8.9 grams of Triton N-57, 2452.6 grams of reagent alcohol (905 ethanol, 5% methanol and 5% isopropanol) and 153.3 grams of p-xylene were charged into a 4L round bottom flask reactor equipped with a mechanical stirring device, a condenser and a thermocouple. The mixture was stirred and mixed at 200 RPM, and the dissolved oxygen in the solution was removed by subsurface purging with nitrogen. After the dissolved oxygen was below 1 ppm, 2.1 grams of azobisisobutyronitrile and 105 grams of divinylbenzene were charged into the reaction. The reaction temperature was raised to 70°C and maintained at this temperature for 20 hours.

[0190] Primary nuclear growth: When the reaction time of 20 hours is reached, the temperature is maintained at 70°C and 1.8 g of azobisisobutyronitrile is added. Subsequently, a solution of 67.6 g of divinylbenzene and 20.3 g of PVP-40 in 202.7 g of reagent alcohol is metered in via a pump at a constant flow rate over 120 minutes. The reaction is continued at 70°C for at least 12 hours. After the reaction, the particles are separated from the reaction slurry by filtration and subsequently washed with methanol, tetrahydrofuran (THF) and acetone. The final product is placed in a vacuum oven and dried overnight at 45°C. Approximately 147 g of 1.95 μm particles are obtained.

[0191] To test the effect of adjusting the amount of PVP-40 at the beginning of the reaction, three different amounts were evaluated (65.1 g - Sample 1A; 48.9 g - Sample 1B; and 109.2 g - Sample 1c). Table 1 below provides the results, which show that particle size is negatively correlated with the amount of PVP-40. Examples 1A to 1C describe the synthesis of poly(DVB80) particles with different particle sizes by adjusting the amount of PVP-40 at the beginning of the reaction. Examples 2A to 2C describe the synthesis of poly(DVB80-co-styrene) particles with different DVB80 and styrene compositions, which are different by adjusting the amount of DVB80 and styrene charged in the primary core synthesis step of the core growth step.

[0192]

[0193] Table 1

[0194] Example 2: Nonporous Poly(DVB80-co-styrene) Particle Core

[0195] In this example, an exemplary non-porous core was fabricated that included a polymer core comprising two different polymers. Other methods and other materials may be utilized to fabricate the non-porous polymer core of the composite particles of the present technology.

[0196] The inhibitors in divinylbenzene (80%, technical grade) and styrene used in the particle synthesis were removed by passing the monomers through an alumina filter cartridge.

[0197] Primary Particle Synthesis: In this particle synthesis experiment (Sample 2A), 78.2 grams of PVP-40, 8.9 grams of Triton N-57, 2452.6 grams of reagent alcohol (905 ethanol, 5% methanol and 5% isopropanol) and 153.3 grams of p-xylene were charged into a 4L round bottom flask reactor equipped with a mechanical stirrer, condenser and thermocouple. The mixture was stirred and mixed at 200 RPM, and the dissolved oxygen in the solution was removed by subsurface purging with nitrogen. After the dissolved oxygen was below 1 ppm, 2.1 grams of azobisisobutyronitrile, 42 grams of divinylbenzene (80%, technical grade) and 63.0 grams of styrene were charged to the reaction. The reaction temperature was raised to 70°C and maintained at this temperature for 20 hours.

[0198] Primary nucleus growth: When a reaction time of 20 hours is reached, the temperature is maintained at 70°C and 1.8 g of azobisisobutyronitrile is added. Subsequently, a solution of 67.6 g of divinylbenzene and 19.2 g of PVP-40 in 192.0 g of reagent alcohol is metered in via a pump at a constant flow rate over 120 minutes. The reaction is continued at 70°C for at least 12 hours. After the reaction, the particles are separated from the reaction slurry by filtration and subsequently washed with methanol, tetrahydrofuran (THF) and acetone in sequence. The final product is placed in a vacuum oven and dried overnight at 45°C. Approximately 135 g of 2.2 μm particles are obtained.

[0199] In Table 2 below, samples 2A to 2C describe the synthesis of poly(DVB80-co-styrene) particles having different compositions of DVB80 and styrene by adjusting the amounts of DVB80 and styrene charged in the primary nucleus synthesis step of the nucleus growth step. The particle size distribution of the poly(DVB80-co-styrene) of sample 2C is described in Figure 6 , and a microscopic image of the particles is depicted in Figure 7 middle.

[0200]

[0201]

[0202] Table 2

[0203] Example 3: A larger particle core made from another smaller core

[0204] In this example, an exemplary nonporous core was fabricated that included a core fabricated in two stages.Other methods and other materials may be utilized to fabricate the nonporous polymer core of the composite particles of the present technology.

[0205] 120 grams of particles (particle size, 2.32 μm) prepared by the method described in Sample 2D were redispersed in a solution containing 37.0 grams of PVP-40, 4.5 grams of Triton™ N-57, 100.0 grams of p-xylene, and 1234.0 grams of reagent alcohol (90% ethanol, about 5% methanol, and about 5% isopropanol) and then loaded into a 4-liter kettle reactor equipped with a mechanical stirring device, a condenser reactor, and a thermocouple. The slurry was mixed at 200 RPM and nitrogen was purged through the surface to obtain dissolved oxygen below 1 ppm. Once the dissolved oxygen in the solution was below 1 ppm, the nitrogen subsurface sparge was changed to a blanket sparge, the stirring speed was adjusted to 75 RPM, and the reaction temperature was then increased to 70°C. When the reaction temperature reached 70°C, 4.8 grams of divinylbenzene (80%, de-inhibited with alumina) and 3.0 grams of AIBN were added. After 15 minutes, a solution containing 139.5 g of divinylbenzene (80%, with alumina to remove inhibitors), 105.6 g of PVP-40 and 1345.7 g of reagent alcohol was added by a pump at a constant rate over 2 hours. After addition, the reaction was maintained at 70°C for 20 hours. After the reaction, the particles were separated from the reaction slurry by filtration. The particles were then washed with methanol, followed by tetrahydrofuran (THF) and finally with acetone. The final product was placed in a vacuum oven and dried overnight at 45°C. 250 g of monodisperse 3.0 μm particles were obtained.

[0206] Example 4: Core surface primer with silane functional groups

[0207] In this example, an exemplary primed nonporous core was fabricated.Other methods and other materials may be utilized to fabricate the primed nonporous polymer core of the composite particles of the present technology.

[0208] The inhibitors in divinylbenzene (80%, technical grade) and styrylethyltrimethoxysilane were removed by passing through an alumina filter cartridge. The reagent alcohol used in the reaction contained 90% ethanol, about 5% methanol and about 5% isopropanol. In this particle synthesis experiment (see sample 4A in Table 3 below), 44.7 grams of PVP-40 and 165.2 grams of p-xylene were loaded into a 4L round-bottom flask reactor equipped with a mechanical stirring device, a condenser reactor and a thermocouple. A slurry of 145.0 grams of particles (sample 1A, from Example 1) in 1490.7 grams of reagent alcohol was added. The mixture was mixed at 200RPM for 24 hours. The reaction slurry was then purged subsurface with nitrogen to obtain dissolved oxygen below 1ppm. Once the dissolved oxygen in the solution was less than 1ppm, the reaction mixture was heated to 70°C and the stirring speed was adjusted to 75RPM. Then, 2.9 grams of divinylbenzene and 2.5 grams of 2,2'-azobis(2-methylpropionitrile) (AIBN) were added. After mixing for 15 minutes, a solution containing 14.5 grams of styrylethyltrimethoxysilane, 1.5 grams of divinylbenzene and 13.9 grams of PVP-40 in 464.0 grams of reagent alcohol was added at a constant flow rate over 2 hours. After the reaction was maintained at 70°C for a total of 20 hours, the reaction was cooled to below 40°C and the resulting particles were separated from the reaction slurry by filtration. The particles were then washed with methanol, followed by tetrahydrofuran (THF) and finally acetone. The final product was placed in a vacuum oven and dried overnight at 45°C. 149.0 grams of primed particles were obtained.

[0209] Table 3 provides the synthesis of primer particles with different surface morphologies and primer thicknesses by adjusting the amount of primer monomer and the amount of crosslinker DVB80 used in a number of different samples. Figures 8 to 13 Primed particles with different surface morphologies and primer thicknesses according to the following samples are shown. Figure 8 and Fig. 9 Primed particles of Sample 4G are depicted. Fig.10 and Fig.11 Primed particles of sample 4H are depicted. Fig.12 and Fig.13 Primed particles of Sample 4I are depicted.

[0210]

[0211] Table 3

[0212] Example 5: Core surface primer with other functional groups

[0213] In this example, exemplary primed nonporous cores with various functional groups were fabricated.Other methods and other materials may be utilized to fabricate the primed nonporous polymer cores of the composite particles of the present technology.

[0214] Here, with reference to sample 5A (as shown below), the primer monomer of the primer-free polymer core is replaced. Specifically, the reagent alcohol used in the reaction contains 90% ethanol, about 5% methanol and about 5% isopropanol. In this particle synthesis experiment, 15.4 grams of PVP-40 and 57.0 grams of p-xylene are loaded into a 1L round-bottom flask reactor equipped with a mechanical stirring device, a condenser, a reactor and a thermocouple. Add 50.0 grams of a slurry of particles made in Example 3 in 514.0 grams of reagent alcohol. The mixture was mixed at 200RPM for 24 hours. The reaction slurry was then purged subsurface with nitrogen to obtain dissolved oxygen below 1ppm. Once the dissolved oxygen in the solution is less than 1ppm, the reaction mixture is heated to 70°C and the stirring speed is adjusted to 75RPM. Then, 1.8 grams of divinylbenzene and 0.9 grams of 2,2'-azobis(2-methylpropionitrile) (AIBN) were added. After mixing for 15 minutes, a solution containing 9.0 grams of N-vinyl pyrrolidone, 0.9 grams of divinyl benzene and 3.6 grams of PVP-40 in 120.0 grams of reagent alcohol was added at a constant flow rate over 2 hours. After the reaction was maintained at 70°C for a total of 20 hours, the reaction was cooled to below 40°C and the resulting particles were separated from the reaction slurry by filtration. The particles were then washed with methanol, followed by tetrahydrofuran (THF) and finally acetone. The final product was placed in a vacuum oven and dried overnight at 45°C. 54.0 grams of primed particles were obtained.

[0215] Samples 5A to 5E, shown below, describe the synthesis of primed particles with different surface functional groups. In each sample, the primer monomer was replaced in the formulation of the primed nonporous polymer core. While the above experiments utilized sample 5A, additional experiments were performed utilizing samples 5B to 5E. Fig.14 and Fig.15 depicts the particles before priming, and Fig.16 and Fig.17 Depicted are the morphological changes of particles after priming with poly(N-vinylpyrrolidone).

[0216]

[0217] Example 6: Nonporous Hybrid Coating on Trimethoxysilane Primer Core

[0218] In this example, an exemplary primed nonporous core with a hybrid coating was fabricated to form a core-shell particle according to the present technology.Other methods and other materials may be utilized to fabricate the primed nonporous polymer core with a hybrid coating of the composite particles of the present technology.

[0219] In this particle synthesis experiment (i.e., for Sample 6A), a 5 L round bottom flask reactor equipped with a mechanical stirring device, condenser, reactor, and thermocouple was set up in an ultrasonic bath capable of heating (490 watts). 140.0 grams of silane primed cores (Sample 4A) were redispersed in 1120.0 grams of 200 proof ethanol and then loaded into the reactor. 1120.0 grams of toluene and 26.9 grams of Pluronic F127 and 77.1 grams of ammonium hydroxide (28%-30% aqueous solution) were added to the slurry in the reactor. The temperature of the ultrasonic bath was raised to 35°C and ultrasonic treatment was started. Ultrasonic treatment was maintained throughout the coating process. When the temperature of the ultrasonic bath reached 35°C, a solution containing 98.2 g of tetraethyl orthosilicate (TEOS), 41.8 g of 1,2-bis(triethoxysilyl)ethane (BTEE), and 3.5 g of Pluronic F127 in a mixed solvent of 70.0 g of ethanol (200 proof) and 70.0 g of toluene was metered into the reactor at a constant flow rate over 6 hours. After addition, the reaction was maintained at 35°C for 24 hours. The coated particles were isolated by filtration and washed 6 times with methanol. The final product was placed in a vacuum oven and dried overnight at 70°C. 174.0 g of non-porous BEH coated particles (i.e., sample 4A particles coated with non-porous BEH material) were obtained.

[0220] Table 4 below provides the synthesis of nonporous hybrid coated particles (Samples 6A-6H) with different coating thicknesses and surface morphologies by adjusting the amounts of TEOS, BTEE and with or without the use of surfactant. Fig.18 and Fig.19 Non-porous hybrid coated particles of samples 6D and 6H are depicted, respectively, showing hybrid coated particles with different coating thicknesses and surface morphologies.

[0221]

[0222] Table 4

[0223] Example 7: Nonporous Hybrid Coating on Pyrrolidone Primed Core

[0224] In this example, an exemplary primed (primed with pyrrolidone) nonporous core with a hybrid coating was fabricated.Other methods and other materials may be utilized to fabricate the primed nonporous polymer core with a hybrid coating of the composite particles of the present technology.

[0225] A 5L round bottom flask reactor equipped with a mechanical stirring device, condenser, reactor and thermocouple was set up in an ultrasonic bath capable of heating (490 watts). 14.0 grams of pyrrolidone primed cores (Sample 5A) were redispersed in 112.0 grams of 200 proof ethanol and then loaded into the reactor. 112.0 grams of toluene, 2.7 grams of Pluronic F127 and 7.7 grams of ammonium hydroxide (28%-30% aqueous solution) were added to the slurry in the reactor. The ultrasonic bath temperature was raised to 35°C for ultrasonic treatment. The ultrasonic treatment was maintained throughout the coating process. When the ultrasonic bath temperature reached 35°C, a solution containing 9.8 grams of tetraethyl orthosilicate (TEOS), 4.2 grams of 1,2-bis(triethoxysilyl)ethane (BTEE), 0.4 grams of Pluronic F127 in a mixed solvent of 7.0 grams of ethanol (200 proof) and 7.0 grams of toluene was metered into the reactor at a constant flow rate over 6 hours. After addition, the reaction was kept at 35°C for 24 hours. The coated particles were isolated by filtration and washed 6 times with methanol. The final product was dried in a vacuum oven at 70°C overnight. 16.0 g of non-porous BEH coated particles were obtained.

[0226] Example 8: Growth of a porous hybrid shell on a polymer core coated with a non-porous hybrid material

[0227] In this example, a nonporous core having a nonporous hybrid coating and a porous hybrid shell was fabricated.Other methods and other materials may be utilized to fabricate the primed nonporous polymer core having a hybrid coating of the composite particles of the present technology.

[0228] In a 1L round-bottom flask equipped with a mechanical stirring device, a condenser and a thermocouple, 5.0 grams of nonporous hybrid coated core (Example 6A, 2.05 μm) were dispersed in 306.8 grams of ethanol and 150.8 grams of water together with 9.0 grams of Pluronic P123. The temperature of the reaction slurry was raised to 46°C and the stirring speed was adjusted to 150 RPM. A solution was prepared by dissolving 5.7 grams of Pluronic P123 in a binary solvent of 113.6 grams of ethanol and 100.5 grams of water, followed by adding an organic mixture containing 12.1 grams of N,N-dimethylhexadecylamine, 14.03 grams of tetraethyl orthosilicate (TEOS), 5.97 grams of 1,2-bis(triethoxysilyl)ethane (BTEE) and 36.0 grams of toluene. The solution was emulsified by ultrasound and the resulting emulsion was mixed at ambient temperature for 60 minutes. After mixing for 60 minutes, the emulsion was added to the reaction and the reaction was continued at 46°C for 24 hours. After the reaction, the particles were separated by filtration and washed three times with methanol. The particles were further aged at 55°C in a solution containing 135.0 grams of ethanol, 122.0 grams of water and 30.0 grams of ammonium hydroxide (28 wt% to 30 wt%) for 24 hours. After drying overnight at 45°C in a vacuum oven, 9.9 grams of 2.85 micron aged core-shell particles were obtained. The average pore size of these particles measured by nitrogen adsorption porosimetry was The surface area is 212.7m 2 / g, and the pore volume is 0.34cc / g.

[0229] Fig. 20 and Fig.21 The surface morphology of the nonporous hybrid coated particles of Sample 6A is depicted. Fig. 22 and Fig.23 The surface morphology of the porous hybrid coated particles of Example 6A is depicted.

[0230] Example 9: Pore size expansion of porous shell

[0231] In order to increase the pore size within the shell, 8 grams of the resulting particles (Example 8) were dispersed in 100 mL of 0.3 M Trizma buffer adjusted to pH = 9.8 with acetic acid. The slurry was transferred to an autoclave reactor and the autoclave reactor was sealed. Pore enlargement was performed by mixing the reaction slurry at 200°C for 18 hours. After 18 hours, the particles were separated by filtration and washed with Milli-Q water until the collected filtrate was neutral. The particles were further washed three times with acetone and dried in a vacuum oven at 70°C overnight. The dried particles were treated with acid by refluxing in 1 M hydrogen chloride overnight. The particles were separated again by filtration and washed with water until the filtrate was neutral. Finally, the particles were washed three times with acetone and dried in a vacuum oven at 70°C overnight. The average pore size of the resulting particles measured by a nitrogen porosimeter is The pore volume was 0.31 cc / g. Comparison of the pore volume and average pore size of the particles of Example 9 and Example 8 illustrates the enlargement of the pores achieved using the technique described in Example 9. Fig.24 is a SEM image of the particles obtained in Example 9. Fig.25 is a SEM image of a cross section of the particles obtained in Example 9.

[0232] Example 10: C18 binding phase on hybrid porous shell

[0233] In this example, a binding material (i.e., C18 binding phase) was added to the outer surface of the hybrid porous shell. To prepare this core-shell particle, 7.5 grams of the particles described in Example 10 were dispersed in toluene (10 mL / g) under anhydrous conditions with octyldecyltrichlorosilane (tC18). The catalyst (imidazole; 10 μmol / m 2 ) was added together with octyldecyltrichlorosilane. The reaction was heated to 110°C for 20 hours and then cooled to room temperature (RT). The particles were separated by filtration and then washed with toluene, acetone and water. After the bonding reaction, ammonium bicarbonate (100mM) and acetone (40:60v / v) were used for hydrolysis at 50°C for 2 hours. The reaction was cooled to RT and the particles were separated by filtration. The particles were then washed with toluene, acetone and water and then vacuum dried at 70°C for 16 hours. The remaining surface silanols were removed using (N,N-dimethylamino)triethylsilane (TES; 5μmol / m 2 ) and (N,N-dimethylamino)trimethylsilane (TMS; 8 μmol / m 2 ) was capped in toluene (10 mL / g) at 110° C. for 4 hours. The particles were isolated by filtration, then washed with toluene, acetone and water, and dried in vacuo at 70° C. for 16 hours.

[0234] Example 11: Chromatographic separation of small molecules on C18-bound hybrid core-shell particles

[0235] Fig.26 is a chromatogram of an isocratic reversed phase separation of thiourea, naphthalene, and acenaphthene using a column packed with the particles from Example 10 as the stationary phase. A 2.1 mm (ID) x 50 mm (length) column was packed with the particles described in Example 10. An isocratic reversed phase separation of a mixture of 0.01 mg / mL thiourea, 0.10 mg / mL naphthalene, and 0.20 mg / mL acenaphthene was then performed on a UPHPLC system (Waters Acquity UPLC system, purchased from Waters Corporation, Milford, MA). The injection volume was 0.3 μL, the flow rate was 0.25 mL / min, the temperature was 30°C, and a mobile phase of acetonitrile / water (60 / 40, v / v) was used. As Fig.26As shown, high efficiency separation is achieved using symmetrical peak shapes. The peak results for the thiourea peak are as follows: RT 0.376, USP plate 7696, RPH 2.71, USP tail number 1.107, and K prime 0 at 1800 column psi. The peak results for the naphthalene peak are as follows: RT 0.663, USP plate 11101, RPH 1.81, USP tail number 1.203, and K prime 0.763 at 1800 column psi. The peak results for the acenaphthene peak are as follows: RT 0.892, USP plate 12025, RPH 1.73, USP tail number 1.174, and K prime 1.373 at 1800 column psi.

[0236] Example 12: Chromatographic separation of dsDNA on C18-bound hybrid core-shell particles

[0237] In this example, another small molecule sample was separated using the particles obtained in Example 10. A 2.1 mm (ID) x 50 mm (length) column was packed with the particles described in Example 10. A gradient ion-paired reversed phase separation of an 18-fragment dsDNA sample was performed on a Waters Acquity UPLC system. To test the results of the particles of the present invention, the same sample was separated using the same conditions and system - the only difference was the type of particles used: Example 10 particles versus silica-based core-shell particles. The column packed with Example 10 showed superior separation performance compared to a leading commercial column packed with silica-based core-shell particles. Fig.27A (Silica core-shell particles) Fig.27B (Core-shell particles of Example 10) for comparison.

[0238] The following conditions were used for silica core separation and particle separation of Example 10: The column temperature was set to 50°C, the sample was delivered using a flow rate of 0.2 mL / min, and the mobile phase was delivered in a gradient format: mobile phase A was 0.1 M TEAA, pH 7, and mobile phase B was 20% acetonitrile in mobile phase A. The gradient was from 57.5 to 84.5 B in 20 minutes. A PDA detector at 260 nm was used to capture the results.

[0239] Example 13: Alkaline stability of C18-bound hybrid core-shell particles

[0240] In addition to comparing the chromatographic results between the particles of Example 10 and the silica core-shell particles (see Example 12), alkaline stability was also evaluated. In this example, a 2.1 mm (ID) × 50 mm (length) column was filled with the particles described in Example 10. The column was treated as follows: (1) pH = 8.0 buffer was passed through the column at a flow rate of 0.2 mL / min for 15 hours; (2) pH = 10.5 buffer was passed through the column at a flow rate of 0.2 mL / min for 15 hours; (3) pH = 12.5 buffer was passed through the column at a flow rate of 0.2 mL / min for 15 hours. At the end of each treatment, a gradient ion-paired reversed-phase separation of an 18-fragment dsDNA sample was performed on a Waters Acquity UPLC system. The column filled with Example 10 showed minimal loss of separation performance when treated at pH = 10.5. The same three treatments were combined with a 2.1 mm (ID) × 50 mm (length) column filled with silica core-shell particles. Although the leading commercial silica-based core-shell particle packed column (treated at pH = 10.5) showed significantly reduced retention time, it provided much worse resolution than the core-shell particles of Example 10. After exposure to pH = 12.5 for 15 hours at 50°C, the column packed with Example 10 still showed good separation of all 18 dsDNA fragments. In comparison, the silica-based core-shell particle packed column completely lost separation when the column was treated under the same conditions. Fig.28A , Fig.28B and Fig.28C Results for three different treatments of the particles of Example 10 are provided; and Fig.29A , Fig.29B and Fig.29C Results for three different treatments of silica core-shell particles are presented.

Claims

1. A core-shell particle, comprising: a nonporous polymer particle core having a modified surface; a nonporous organic-inorganic hybrid material in contact with the modified surface; and A porous organic-inorganic hybrid shell material is in contact with the non-porous organic-inorganic hybrid material.

2. The particle of claim 1, wherein the non-porous polymer particle core is made from one or more free radical polymerizable monomers.

3. The particle of claim 2, wherein the nonporous polymer particle core is made of styrene, divinylbenzene, methacrylate or acrylonitrile.

4. The particle of claim 1, wherein the nonporous polymer particle core is made from one or more monomers containing at least two functional groups.

5. The particle of claim 2, wherein the nonporous polymer particle is prepared from monomers by condensation.

6. The particle of claim 5, wherein the monomer is a carboxylic acid / alcohol or a carboxylic acid / amine.

7. The particle of claim 1, wherein the nonporous polymer particle core is made from one or more monomers that are polymerizable by ring-opening polymerization.

8. The particle of claim 7, wherein the monomer is an epoxide.

9. The particle of claim 1, wherein at least a portion of the modified surface of the nonporous polymer particle core comprises at least one functional group covalently bonded to the nonporous organic-inorganic hybrid material to form a functionalized surface.

10. The particle of claim 9, wherein the functional group is at least one of an organosilane characterized by a C-Si, an organotitanium characterized by a C-Ti, and an organozirconium characterized by a C-Zr bond.

11. The particle of claim 1 , wherein at least a portion of the modified surface of the nonporous polymer particle core comprises at least one functional group that electrostatically interacts with the nonporous organic-inorganic hybrid material to form a functionalized surface.

12. The particle of claim 11, wherein the functional group is an amide.

13. The particle of claim 1, wherein the nonporous organic-inorganic hybrid material has a thickness in a range of about 10 nm to about 200 nm.

14. The particle of claim 1, wherein the nonporous organic-inorganic hybrid material has a thickness in a range of about 25 nm to about 100 nm.

15. The particle of claim 1, wherein the nonporous organic-inorganic hybrid material has a pore volume of less than 0.1 cc / g.

16. The particle of claim 1, wherein the nonporous organic-inorganic hybrid material comprises at least one of silica, alumina, titanium, cerium, zirconium, zirconia, or a ceramic material.

17. The particle of claim 1, wherein the nonporous organic-inorganic hybrid material comprises a silicon-based organic-inorganic hybrid material.

18. A core-shell particle, comprising: a nonporous polymer particle core having a modified surface; a nonporous organic-inorganic hybrid material in contact with the modified surface; a porous organic-inorganic hybrid shell material in contact with the nonporous organic-inorganic hybrid material; as well as A bonding material is in contact with the porous organic-inorganic hybrid shell material.

19. The particle of claim 18, wherein the binder material is incorporated within the porous organic-inorganic hybrid shell material.

20. The particle of claim 19, wherein the binding material is further deposited on an outer surface of the porous organic-inorganic hybrid shell material.

21. The particle of claim 19, wherein the binder material is uniformly incorporated.

22. The particle of claim 19, wherein the binder material is incorporated in a gradient.

23. The particle of claim 18, wherein the binding material is further in contact with the nonporous organic-inorganic hybrid material.

24. The particle of claim 23, wherein the binder material is incorporated within the nonporous organic-inorganic hybrid material, deposited on an outer surface of the nonporous organic-inorganic hybrid material, or a combination thereof.

25. The particle of claim 24, wherein the binder material is uniformly incorporated within the nonporous organic-inorganic hybrid material.

26. The particle of claim 24, wherein the binding material is incorporated into the nonporous organic-inorganic hybrid material in a gradient.

27. The particle of claim 18, wherein the binding material is further in contact with the modified surface.

28. The particle of claim 27, wherein the binding material is incorporated into the modified surface, deposited on the modified surface, or a combination thereof.

29. The particle of claim 28, wherein the binding material is uniformly incorporated within the modified surface.

30. The particle of claim 28, wherein the binding material is incorporated into the modified surface in a gradient.

31. The particle of claim 23, wherein the binding material is further in contact with the modified surface.

32. The particle of claim 31, wherein the binding material is incorporated into the modified surface, deposited on the modified surface, or a combination thereof.

33. The particle of claim 32, wherein the binding material is uniformly incorporated within the modified surface.

34. The particle of claim 32, wherein the binding material is incorporated into the modified surface in a gradient.

Citation Information

Patent Citations

  • Polymer particles with a gradient composition and methods of production thereof

    US20190322783A1

  • Preparation of organically modified silicon dioxides

    US4017528A

  • Porous hybrid particles with organic groups removed from the surface

    US6528167B2

  • Porous inorganic / organic hybrid particles for chromatographic separations and process for their preparation

    US6686035B2

  • Porous hybrid particles with organic groups removed from the surface

    US7175913B2